Fabrication and application of carbon sequestration grouting material for sealing leakages in mine strata - Jing Mei; Jianwei Cheng; Shuping Sheng; Yejiao Liu; Zhiyuan Ma; Qiang Fu; Dezhi Ran (European Journal of Environmental and Civil Engineering, 2026)

Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Engineered lipase enables selective hydrolysis of palmitic over oleic acyl chains at a two‑phase microfluidic interface - Jin-Zheng Wang; Lu Tan; Cheng-Kun Wu; Xin-Ying Wang; Kheng Lim Goh; Richard Ansah Herman; Shuai You; Sheng Sheng; Fu-An Wu; Jun Wang (Bioresource Technology, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Immunogenicity and post-challenge virological outcomes of a multivalent subunit vaccine in sheep challenged with cytopathic BVDV-1a - Zhiran Shao; Jing Yuan; Yuhao Li; Lu Xiao; Rongrong Ni; Yinuo Li; Yalin Gao; Zeyao Wang; Yuting Zhang; Aodi Wu; Maoyuan Gu; Junyuan Li; et al. (Veterinary Microbiology, 2026)

Phenethyl isothiocyanate mediates autophagy via the AMPK/mTOR signal pathway in human glioblastoma multiforme cells - Shu-Fen Peng; Hsin-Chung Liu; Fu-Shin Chueh; Hsu-Tung Lee; Sheng-Yao Hsu; Jaw-Chyun Chen; Jing-Gung Chung; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Predicting citywide human mobility with a graph-prior-enhanced euclidean convolutional network - Sheng Wu; Linbaizhi Wang; Peixiao Wang; Hengcai Zhang; Shifen Cheng; Xin Fu; Junhao Guo; Feng Lu (Sustainable Cities and Society, 2026)

Phosphorus legacy advances the negative response of surface soil organic carbon to altered precipitation regimes - Qiao Liu; Fangchao Wang; Fu-Sheng Chen; Junjie Huang; Shengnan Wang; Jianjun Li; Xiangjiang Liu; Zeqing Ma; Huiming Wang; Xiaofei Hu; Yiqi Luo (Soil Biology and Biochemistry, 2026)

Residual allergenicity in commercial partially and extensively hydrolyzed infant formulas: A combined immunological and mass spectrometric study - Qiaozhi Zhang; Feiyang Huang; Aiqian Ye; Jian He; Sufang Duan; Yalu Yan; Huadong Sheng; Zhongshan Gao; Hua Huang; Linglin Fu (Food Chemistry, 2026)

A dynamic adaptive electric field regulation strategy for stabilizing zinc anodes based on σ-electron donation - Hongxiang Zhao; Hua Yang; Jiayu Li; Yanwei Fu; Yu Zhao; Yuanshuai Wan; Yue Li; Yuliang Pang; Xingfa Qiu; Wenwen Duan; Weize Wang; Jiali Zhang; et al. (Chemical Engineering Journal, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Dominant mechanisms controlling sand liquefaction resistance under foreshock sequences - Sheng Zhang; Guangqing Liu; Xueqian Ni; Wenbo Xie; Hongjian Fu; Zhao Zhang; Feng Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

The hidden cost of green food packaging: Biodegradable plastics release more micro/nanoplastics and enhance PFAS co-exposure - Qiaozhi Zhang; Sheng Lan; Kan Jiang; Yongning Wu; Qi Zhang; WenJiabao Wen; Hongyan Li; Linglin Fu (Journal of Hazardous Materials, 2026)

Unraveling the cholesterol-lowering mechanism of a Lactobacillus rhamnosus S_82 and xylo-oligosaccharides synbiotic in sour cream - Xuemeng Fu; Wenhao Zhao; Dongyao Li; Na Zhang; Miaoshu Wang; Xia Tang; Qinghai Sheng; Hongtao Tian; Chen Li (Food Microbiology, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Synergistic regulation of bimetallic d-band centers in NiM-NiMOx (M = Co/Cu) catalysts toward enhancing selective hydrogenation - Liangmin Ning; Jun Xie; Shiyan Sheng; Jiawen Wang; Tianyu Zhang; Shuai Li; Shuanglu Fu; Tianqi Xie; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Clay mineral-facilitated azo dye biodecolorization: Mineral-specific electron transfer pathway and microbial community response - Ying Zhang; Wei Yin; Tian-Lei Zhao; Yi-Ming Ding; Ling-Xiong Yuan; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Applied Clay Science, 2026)

Persistent regional hot-dry extremes identified by a novel cascading compound index and their possible association with ENSO transitions - Qimin Deng; Louise J. Slater; Christian L. E. Franzke; Yixuan Guo; Wuke Wang; Zuntao Fu; Boen Zhang; Sheng Wu (Climate Dynamics, 2026)

Theoretical and Numerical Simulation Study on Coal Pillar Width and Energy Evolution of Gob-side Entry Driving in Deep Thick Coal Seams - Fu-zhou Qi; Jian-hui Liu; Wei-jian Liu; He-bin Zhang; Kai Wang; Shui-sheng Yu; Xiang-yun Ma (Applied Geophysics, 2026)

Outcome-specific park-catchment assessment of age-supportive neighborhood parks using field audits and street-view imagery - Li-Chih Ho; Yu-Sheng Shen; Sin-Rou Fu; Po-Ju Chang (Landscape and Ecological Engineering, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Depositional and Diagenetic Controls on Eyelid–Eyeball Limestones in the Middle Permian Maokou Formation, Sichuan Basin - Zhipeng Chen; Penghui Xie; Lei Chen; Sheng Fu; Gaocheng Wang; Liwei Jiang; Chen Zou (Journal of Marine Science and Engineering, 2026)
The Mao-1 Member of the Middle Permian Maokou Formation in the Yongchuan area contains distinctive eyelid–eyeball limestones developed in an outer-ramp to intraplatform-basin transitional setting. The two components alternate as mud-rich laminae and carbonate-rich nodules or layers. Eyelid limestone contains 10–45% micritic carbonate mud and a mean total-grain content of 69.11%, whereas eyeball limestone contains

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Study on calculation methods for predicting the ultimate uplift bearing capacity of pressure-cast-in-situ pile with spray-expanded frustum (PPSF) - Sheng-shi Qiao; Qian-qing Zhang; Jun-wei Liu; Yuan-chen Huang; Tao Fu (Transportation Geotechnics, 2026)

Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Unveiling the dynamic electron transfer at asymmetric Fe-O-Co sites for sustained PMS activation via in-situ synchrotron spectroscopy - Xian-Chuan Chen; Fu-Sheng Sun; Cong-Qiang Liu; Guang-Hui Yu (Journal of Environmental Sciences, 2026)

Particle-Size Control of Radionuclide Enrichment and Environmental Risk Pathways in Slurry from the Wandan Mud Volcano - Chih-Chung Lin; Yu-Sheng Wang; Wei-Hsiang Huang; Ting-Chien Chen; Yuan-Fu Lu (Environmental Pollution, 2026)

A mesomechanics-based constitutive model for coarse-grained soils considering particle breakage and grian-size effect - Lu Sun; Sheng Wang; Fu Cao; Enlong Liu; Fei Luo (Computers and Geotechnics, 2026)

Multi-responsive and pressure-sensing soft actuator based on MXene/PDMS bilayer film with micro-ridge structures - Bo Ma; Sheng-Bo Sang; Pu Song; Jia-Hui Zhang; Qian Zhao; Hong-Tao Wang; Hui Gao; Xiu-Yan Fu; Zheng-Xiao Wang; Jia-Nan Ma (Chemical Engineering Journal, 2026)

Deciphering Er3+ energy level population in La2Sn2O7 nanocrystals via tailored short-range energy transfer for multidimensional applications - Jiamei Ren; Bin Duan; Kejie Li; Jiaqi Zhao; Dongxu Guo; Ruiying Lu; Tianqi Sheng; Zuoling Fu (Chemical Engineering Journal, 2026)

Can perceptual strain index predict physiological strain? A human-participant experiment in low-intensity activity with moisture impermeable protective clothing - Sheng He; Jie Yang; Song Chen; Feifan He; Jialin Wu; Xin Zheng; Ming Fu; Yayun Li; Wenguo Weng (Building and Environment, 2026)

An improved method for Gill’s hematoxylin and eosin staining based on the optimal acetic acid ratio - Zhijie Ma; Caixia Sheng; Danju Wu; Huimin An; Wen Tang; Ping Zhao; Guoxiang Fu (Histochemistry and Cell Biology, 2026)

Identification and Motion Trajectory Analysis of High-Position Dangerous Rock Mass in the Lanhuazhai Collapse Triggered by the 2022 Luding Ms 6.8 Earthquake - Jingyu Kang; Xiaodong Fu; Kai Wu; Qian Sheng; Xing Wang; Miao Liang; Shuai Huang (Journal of Earth Science, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

ACSL1 orchestrates ferroptosis and degranulation in low-density neutrophils: a novel pathogenic mechanism and therapeutic target in systemic lupus erythematosus - Wenqian Wang; Tiancheng Qi; Jinlin Yang; Yirui Fu; Huan Zhang; Xinyue Liang; Zhongkai Zhang; Guoguo Fu; Sheng Gao; Chunyan Hua (Molecular and Cellular Biochemistry, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

Loss of CmMAIL2 compromises chloroplast function but permits developmental progression in melon - Liting Fu; Kexin Chen; Dongyang Dai; Kaihong Hu; Yuxuan Ma; Dandan Li; Yupeng Pan; Hanqiang Liu; Yunyan Sheng (Plant Science, 2026)

The role of water in REE mineralization of carbonatite systems: constraints from apatite and biotite volatiles - Jian-Hui Su; Xin-Fu Zhao; Johannes Hammerli; Sheng-Ren Chang; Xiao-Chun Li; Wen-Lei Song; Mei-Fu Zhou (Geochimica et Cosmochimica Acta, 2026)

Combined pH-shifting and glycosylation treatment enhances functionality and mitigates allergenicity of β-lactoglobulin - Jian Wang; Aiqian Ye; Jian He; Huadong Sheng; Hua Huang; Kan Jiang; Qiaozhi Zhang; Linglin Fu (Food Chemistry, 2026)

Surface wave tomography reveals potential ice-bedrock interaction in the Larsemann Hills, East Antarctica - Changcheng Li; Lei Fu; Zhengbo Li; Kun Luo; Sheng Dong; Hengxin Ren; Xiaofei Chen (Science China Earth Sciences, 2026)

Effects of gradation on particle breakage and mechanical behaviour of coral sand - Yuan-yi Chen; Fu-sheng Zha; Cai-ying Chen; Yi Tang (Transportation Geotechnics, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Suspension-inspired passive stabilization of semi-submersible FOWTs via a phase cancellation mechanism - Hao-Dong Hu; Yin-Fu Jin; Xiang-Sheng Chen; Zhen-Yu Yin (Ocean Engineering, 2026)

Leverage-based nutrient governance for drinking water sources using hydro-ecological zoning and source apportionment in the Yangtze River Basin - Haizhen Hu; Qing Fu; Sheng Chang; Yinying Zhu; Asaad Y. Shamseldin; Fan Zhang; Guang Yang; Chun Ye; Yueting Fan; Enrui Wang (Journal of Environmental Chemical Engineering, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

The Lhasa Terrane: A tale of two origins and its convergence at the Northern Margin of Gondwana - Chang-Sheng Yu; Mei-Fu Zhou; Ming Wang; Jian-Bo Zhou; Wen-Jun Hu (Earth-Science Reviews, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

GABAergic Inhibition from the Nucleus Tractus Solitarius to Ventrolateral Medulla Phox2b Neurons Modulates Central Respiratory Chemoreflex and Ventilatory Homeostasis - Liuqi Shao; Yake Ji; Hongxiao Yu; Zixuan Cheng; Fanrao Kong; Xiaoyi Wang; Bingwen Zhang; Yinchang Wang; Yimeng Song; Fang Yuan; Congrui Fu; Sheng Wang (Neuroscience Bulletin, 2026)

Effect of external application of poly-γ-glutamic acid on the tillering stage of rice under drought stress - Yanfei Wu; Yiming Zhao; Yue Wen; Zixiang Li; Yuquan Fu; Xuezhu Du; Feng Sheng (Cereal Research Communications, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Numerical study on the protective effectiveness of solidified soil protection layer (SSPL) for scour control of offshore pile foundations - Sheng-bang Liu; Ji-fu Yin; Jin-jian Chen; Xiao-ni Wu; Peng-xiang Li (Ocean Engineering, 2026)

Metagenomic analysis of urban water systems uncovers the interplay between antibiotic resistance genes and microbial communities in response to PFAS contamination - Kunfeng Zhang; Sheng Chang; Yinying Zhu; Hongru Shang; Qing Fu; Xiang Tu; Yanling Yu; Yujie Feng (Journal of Hazardous Materials, 2026)

Iron and calcium interaction for soil As remediation in As waste mine site: Risk assessment and In-situ stabilization - Yuliang Zhang; Sheng Li; Pingfeng Fu; Fangxiang Tu; Tao Zhang; Huiqun Yu; Huifen Yang; Tianli Xue; Xi Qin; Chonggao Wei; Lin Liang (Environmental Pollution, 2026)

Study on thermophysiological responses for heavy-load activity in hot environment: factors interaction experiments - Sheng He; Liangchang Shen; Song Chen; Feifan He; Jie Yang; Ming Fu; Jialin Wu; Xin Zheng; Yayun Li; Wenguo Weng (Energy and Buildings, 2026)

Zircon evidence for exogenous water delivery to the lunar interior - Yong Wang; Xiao-Ping Xia; Jian Xu; Yong-Sheng Liu; Christopher J. Spencer; Trevor Ireland; Ze-Xian Cui; Xiao-Jia Zeng; Jan C.M. De Hoog; Aaron J. Cavosie; Bin Fu; Qing Yang; et al. (Earth and Planetary Science Letters, 2026)

A novel fluid–solid interaction framework by coupling three dimensional explicit discontinuous deformation analysis and material point method - Jingyu Kang; Xiaodong Fu; Hao Sheng; Jian Chen; Yongqiang Zhou; Tian Xi (Computers and Geotechnics, 2026)

Research on catastrophic process of large-scale slope using 3D-DDA with machine learning-based parameter optimization - Jingyu Kang; Xiaodong Fu; Hao Sheng; Jian Chen; Xu Cheng (Computers and Geotechnics, 2026)

Electrical–parameter–optimized joule heating of a carbon medium for high–efficiency CO2–to–CO conversion - Zhishang Wang; Zunrong Sheng; Nan Jiang; Chong Li; Zhiguo Zhao; Yongqiang Fu; Wenzhu Wu; Jie Li (Chemical Engineering Journal, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Secondary metabolites from the endophytic fungus Hypoxylon sp. HK-37 derived from Aquilaria sinensis - Zheng-Zhuo Ren; Kai-Lei He; Fei Wu; Li Yang; Jing-Zhe Yuan; Ze-Sheng Li; Hao-Fu Dai; Wen-Jian Zuo; Hui-Qin Chen (Phytochemistry Letters, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Polydisperse polystyrene microplastics exacerbate colitis through gut microbiota-butyrate-PPARγ axis disruption in mice - Zhian Zhai; Ying Yang; Yifei Xu; Qingyao Fu; Sheng Chen; Zhenlong Wu (Journal of Hazardous Materials, 2026)

Multi-component catalysts with three-dimensional porous structures for exhaust gas purification: Activity for soot and CO - Xiaolong Sheng; Li Li; Changcheng Fu; Peng Zhang; Lefu Yang; Mingzhang Pan; Jinkai Gu; Pingping Huang; Yupei Yang; Tian Zhang; Wei Guan (Journal of Environmental Chemical Engineering, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

Long-term cultivation of indica–japonica hybrid rice reshapes the sustainability of rice systems by simultaneously enhancing yield, nitrogen use efficiency, and soil health - Jinjia Gan; Xinyue Xu; Sheng Tang; Kefeng Han; Tao Sun; Jinzhao Ma; Xiangde Yang; Xiu Liu; Haoran Fu; Zhihao Pang; Lingli Mao; Lianghuan Wu; et al. (European Journal of Agronomy, 2026)

Study on progressive collapse resistance of steel beam-column structures with column tree connection under edge column failure - Jian-Gui Qin; Sheng-Yu Lu; Wei-Wei Zhang; Feng Fu; Kai Qian (Engineering Structures, 2026)

A novel gallic acid modification and high-temperature alkali activation mesoporous biochar enables ultrafast and high-capacity removal of short- and long-chain PFAS from water - Kunfeng Zhang; Sheng Chang; Yanling Yu; Hongru Shang; Xiang Tu; Qing Fu; Abdul Qadeer; Yujie Feng (Chemical Engineering Journal, 2026)

High-titanium mare basalts: From petrogenesis to lunar evolution - Haojie Chen; Bin Su; Yi Chen; Sheng Gou; Hengci Tian; Fu-Yuan Wu (Science China Earth Sciences, 2026)

Size and Geometry Effects on the Rock Mixed-Mode I/II Fracture: Insights from the Perspective of 3D Discrete Element Models - Longfei Wang; Huan Liu; Sheng Zhang; Yinan Fu; Zheng Li; Xiaoping Zhou (Rock Mechanics and Rock Engineering, 2026)

Overexpression of As3mt Attenuates Sodium Arsenite Induced Ferritinophagy and Hepatic Lipid Accumulation in Mice - Jia-cheng Bao; Yuan Yang; Yi Wang; Fu-sheng Xie (Biological Trace Element Research, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

When combined frailty, anemia, and malnourishment exhibit a predictive power for 30-day outcomes following anterior cervical discectomy and fusions for cervical spondylotic myelopathy - Jacob M. Gluski; Gabrielle Santangelo; Paul Serrato; Shaila Ghanekar; Ethan DL Brown; Aryaa Karkare; Aladine Elsamadicy; Sheng-fu Larry Lo; Daniel M. Sciubba (Next Research, 2026)

Instantaneous ammonia emissions prediction for light-duty gasoline vehicles using ensemble learning - Jing Wang; Lei Zu; Han Jiang; Huayang Zhao; Haiguang Zhao; Mingliang Fu; Yitu Lai; Yunjing Wang; Sheng Su; Hefeng Zhang; Yan Ding (Fuel, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Effects of walking activity on micro-environment heat convection and thermal comfort in chemical protective clothing - Sheng He; Jie Yang; Feifan He; Song Chen; Jialin Wu; Liangchang Shen; Xin Zheng; Ming Fu; Yayun Li; Wenguo Weng (Building and Environment, 2026)

Electric heavy-duty truck deployment and urban CO2 emissions: Evidence from Chinese policy-induced transitions - Zhonglin Sheng; Xiaozhen Fu; Xu Hao (Transportation Research Part D: Transport and Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Immune modulation of Spodoptera litura larvae parasitized by Meteorus pulchricornis and role of the host β-1, 3-glucan-binding protein in parasitism success - Yan Song; Zhi-Xiang Liu; Feng-ming Gu; Ping Li; Wei-Hong Zhou; Jun Wang; Fu-An Wu; Sheng Sheng (Pesticide Biochemistry and Physiology, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

A new method for constructing dynamic-static conversion models for rock mechanics based on acoustic wave propagation characteristics - Sheng Wang; Kaizhou Xu; Haixue Wang; Xiaofei Fu; Chengxuan Ren (Journal of Applied Geophysics, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Interactive effects of abiotic factors on the ecophysiology characteristics of Aspergillus flavus under future climate conditions - Xuran Fu; Jiadi Sun; Honglin Yan; Xiyu Cao; Chuanzhi Jiang; Jin Ye; Wei Wang; Jia-Sheng Wang; Xiulan Sun (Food Bioscience, 2026)

Corrigendum to “Enhanced persulfate activation via FeS/FeS2 and boron synergized Fe(II)/Fe(III) cycling for trichloroethylene degradation: Experimental and theoretical insights” [Chem. Eng. J. 527 (2026) 172147] - Mudassir Habib; Tehreem Ayaz; Meesam Ali; Muhammad Rizwan; Xianxian Sheng; Muhammad Kashif Javed; Rongbing Fu; Shuguang Lyu (Chemical Engineering Journal, 2026)

Engineering of ethylene glycol (EG)-trophic Escherichia coli enables fast growth on EG for closed-loop PET biodegradation - Jia-Yu Chen; Sheng-Qi Gao; Qing-Song Huang; Xiao-Min Zhao; Qi-Sheng Fu; Kang-Qi Hu; Yan Huang; Jing Wu; Zheng-Fei Yan (Bioresource Technology, 2026)

Biochar reshapes soil bacterial community composition and survival strategies: a meta-analysis revealing trade-offs between microbial stability and functional complexity - Jianwei Li; Jeewani H. Peduruhewa; Robert W. Brown; David R. Chadwick; Robert I. Griffiths; Haoran Fu; Hongfeng Bian; LianXi Sheng; Qinqxu Ma; Davey L. Jones (Biology and Fertility of Soils, 2026)
As a promising strategy for improving soil health and mitigating climate change, biochar has received increasing attention in recent years. However, findings regarding its microbial effects are often context-dependent, and the complex impacts of biochar on soil microbial communities remain inadequately understood. Here, we integrated 843 samples of 16 S rRNA sequencing data from 24 independent studies, utilizing machine learning and co-occurrence network analysis to evaluate general patterns and mechanisms by which biochar alters bacteria community composition and survival strategies. Overall, biochar significantly increased soil organic C, total N, pH, and reduced bulk density, which in turn affected microbial communities. While biochar addition did not notably alter bacterial α-diversity (Shannon index or species richness), it significantly changed β-diversity, indicating that biochar addition altered microbial community composition. Biochar changed community composition and survival strategies by reducing the oligotroph/copiotroph ratio, favouring copiotrophs groups (e.g., Bacteroidota). K -strategists (e.g., Planctomycetota) were reduced by biochar, potentially due to increased nutrient availability and increased competition. Model selection analysis identified that soil physicochemical properties were key drivers of α-diversity, while climate variables were the main factors influencing β-diversity. Biochar properties represented key factors influencing changes in microbial survival strategy. Machine learning identified 138 biomarker genera, with biochar-treated soils showing an increase in Pseudomonadota. Co-occurrence network analysis indicated that biochar increased microbial stability, but reduced network complexity, suggesting a trade-off between resilience and functional redundancy following biochar addition. These findings provide new insights into how biochar influences the composition and ecological functions of soil bacterial communities and offer theoretical support for its scientific application in sustainable soil management.

Effects of inflammatory markers and sleep quality in stroke patients by reducing residential PM2.5 levels: A case-crossover intervention study - Wen-Hua Lee; Chen-Ta Lin; Pei-Chih Wu; Sheng-Fu Liang; Cheng-Yu Lin; Yu-Chun Wang; Shih-Chun Candice Lung; Tain-Junn Cheng (Science of The Total Environment, 2026)

Maize adaptation to low-dose nanoplastic–lead co-contamination: Foliar metabolic reprogramming and phyllospheric microbiome restructuring - Qian Fu; Jin-sheng Shi; Jin-long Lai; Yu Zhang; Yan Huang; Xue-gang Luo (NanoImpact, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Enhanced persulfate activation via FeS/FeS2 and boron synergized Fe(II)/Fe(III) cycling for trichloroethylene degradation: Experimental and theoretical insights - Mudassir Habib; Tehreem Ayaz; Meesam Ali; Muhammad Rizwan; Xianxian Sheng; Muhammad Kashif Javed; Rongbing Fu; Shuguang Lyu (Chemical Engineering Journal, 2026)

Fe-N4 single-atom nitrogen doped carbon catalyst: Dual-functional design for PMS-activated antibiotic degradation and efficient oxygen reduction reaction - Yamin Yang; Limeng Yang; Qi Zhang; Yaru Li; Longsheng Cao; Qingshan Li; Chengyu Fu; Cuihong Sheng; Siyuan Zhang; Haijiao Xie; Pengfei Zhang (Chemical Engineering Journal, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Cordycepin Mitigates Sepsis-Associated Encephalopathy by Promoting Microglial M2 Polarization via the IL-17a/IL-17RA/NF-κB Axis - Ying Yuan; Ganyue Fu; Yunqiang Zhu; Jianning Xu; Fuxing Li; Zhiyong Sheng (Molecular Neurobiology, 2026)

An integrated microfluidic system equipped with a shear force control device for optimized selection of high-affinity, high-specificity aptamers targeting folate receptor alpha - Yang-Sheng Shao; Yi-Cheng Tsai; Chih-Hung Wang; To-Wen Chen; Keng-Fu Hsu; Gwo-Bin Lee (Analytica Chimica Acta, 2026)

High-resolution spatial mapping of electrocorticographic activities with NeuroCam: a 4096-channel, multiplexed flexible thin-film transistor array - Yang Xie; Zepeng Zhang; Muyang Liu; Jinhong Guo; Miao Xu; Lei Zhou; Lei Zhang; Lihao Yao; Xiaolin Zhou; Zhengwei Hu; Liang Ma; Xiaojian Li; et al. (Science Bulletin, 2025)

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Soil microbes benefit enhancing stability of soil organic carbon pools under mixed-species plantations - Yuan Yao; Yue He; Pei Wang; Ruixuan Liu; Mingyue Fu; Jian Feng; Yutong He; Hanying Hu; Sheng Zhang (Journal of Environmental Management, 2025)

Ore-forming mechanism of high-grade iron ore in Qidashan iron deposit, Liaoning Province: insights from the columbite-group minerals in granite and altered rocks - Yu-zeng Yao; Chang-ming Wei; Jing Liu; Jian-fei Fu; Sheng Xu (Journal of Asian Earth Sciences, 2025)

A peptidomics-based investigation of the synergistic effects of neutral and Alcalase proteases on release of antioxidant peptides from soybean protein isolates - Shulong Cai; Liqi Fan; Dan Liu; Changxing Wei; Na Yang; Xichao Fu; Rong Tang; Jucai Xu; Sheng Yin; Xin Chen (Food Chemistry, 2025)

Harpadon nehereus Peptide FF4 alleviates hyperuricemia by regulating uric acid synthetase and transporters, as well as modulating the ROS/NLRP3 signaling pathway - Yang-na Huang; Hui-wen Zheng; Sheng-xiang Zhao; Zhan-ying Zhu; Yong-jie Long; Yue-wen Chen; Jing-jing Fu (Food Bioscience, 2025)

Ohmic contact interface engineering of fullerene-derived long-range ordered porous carbon-based anodes for durable sodium-ion capacitors - Jundong Shao; Mingming Gao; Ying Huang; Songlin Liu; Junke Li; Xiaosong Xiong; Antonio Gaetano Ricciardulli; Sheng Yang; Yubin Fu; Faxing Wang; Chun Fang; Panpan Zhang; et al. (Chemical Engineering Journal, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Pathways regulating changes in soil microbial carbon use efficiency with plant cover and nitrogen addition in a desert of the Tibetan Plateau - Ying Zhao; Jie-Yu Gong; Jiu-Ying Pei; Fu-Qiang Huang; Jian-Sheng Ye (Plant and Soil, 2025)

Crop rotation mitigates soil fungal diversity loss under warming or increased moisture - Zhibo Zhou; Keming Yang; David Tissue; Zhong Wei; Le Li; Zhe Tang; Lukuan Fu; Hanqin Li; Tingting Sheng; Hongwei Liu; Yingjun Zhang; Fengge Zhang (Agriculture, Ecosystems & Environment, 2025)

Full waveform inversion of cross-hole GPR data using Markov Chain Monte Carlo method based on SE-Resnet - Sheng-chao Wang; Yu-fei Wang; Yi-fei Liu; De-fu Zhang; Hui Sun; Gong-min Chen; Xiang-yu Tan (Applied Geophysics, 2025)

PYL2 regulates drought and blast (Magnaporthe oryzae) resistance in rice - Zhensheng Qiao; Yimin Zhao; Xiaorui Wang; Yuquan Fu; Chuming chen; Xuezhu Du; Feng Sheng (Plant Science, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

Identification of RAV transcription factors (B3-domain-containing) and functional analysis of OsRAV2 in rice blast and drought stress - Yuquan Fu; Zhensheng Qiao; Yiming Zhao; Juchen Zhou; Xiangyu Huang; Changhuan Du; Feng Sheng; Xuezhu Du (Journal of Plant Physiology, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Ku proteins play a positive role in the immune response against WSSV infection in Litopenaeus vannamei - Huiling Xing; Wei Xiao; Guoqing Dai; Zhibin Fu; Sheng Ke; Lili Shi (Fish & Shellfish Immunology, 2025)

Evaluation of soil quality and system sustainability in ratoon rice paddy field under green manure application in central China - Ying Xu; Qiwen Hou; Jinbiao Xiang; Mutian Gao; Pufan Shao; Sheng Chen; Zhiqiang Fu; Pan Long; Cheng Huang (Field Crops Research, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Hanging drop culture reprograms mesenchymal stem cell transcriptome to enhance cell delivery efficiency via attenuated pulmonary entrapment - Hsiang-Tzu Lee; Sheng-Yung Fu; Wei-Han Weng; Wei-Chen Chao; Yu-Pao Hsu; Nan-Ping Yang; Yu-Hsu Chen; Shau-Kwaun Chen; Chien-Wen Chang (Drug Delivery and Translational Research, 2025)
The three-dimensional (3D) culture system has emerged as an indispensable platform for modulating stem cell function in biomedicine, drug screening, and cell therapy. Despite a few studies confirming the functionality of 3D culture, the molecular factors underlying this process remain obscure. Here, we have utilized a hanging drop method to generate 3D spheroid-derived mesenchymal stem cells (3D MSCs) and compared them to conventionally 2D-cultured MSCs. The results showed that 3D MSCs exhibited distinct phenotypic features than 2D-cultured MSCs and expressed different transcriptional responses, as found from RNA-Seq analysis. Gene ontology (GO) annotations and KEGG pathway mapping pinpointed that the 3D MSCs responded more actively to incoming signals as they upregulated receptors and cytokine production while downregulating proteolysis-, cytoskeletal-, extracellular matrix-, and adhesion-related genes. Functionally, these MSCs also displayed enhanced chemotaxis and improved pulmonary transgression post-intravenous injection. This study provides mechanistic insights on addressing a significant limitation of MSC therapy: pulmonary entrapment after systemic delivery. Moreover, upregulated pluripotency-associated genes, such as Oct4, Sox2, and Nanog, suggest that the 3D MSCs possessed enhanced stemness and regenerative capacity. The results indicate that 3D spheroid culture reshapes MSC transcriptomic and functional profiles and emerges as a promising strategy for improving their therapeutic potential in regenerative medicine. Graphical abstract

Study on Performance Optimization and Failure Law of Fly Ash-Coal Gangue Backfill - Fu-zhou Qi; Zhen Li; Song Yin; Ju-dong Li; Xiao-yu Liu; Kai Wang; Wei-jian Liu; Shui-sheng Yu; Zhi-liu Wang (Applied Geophysics, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

Freeze-thaw and dry-wet alternation regulate the impacts of Fe-C based passivator on soil heavy metals immobilization - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Environmental Chemical Engineering, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Reassessing the geocentric-axial-dipole (GAD) model for Proterozoic time with paleomagnetic directions from dike swarms - Zheng Gong; David A.D. Evans; Roger R. Fu; Sheng Xu (Earth and Planetary Science Letters, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

Prognostic Significance and Immune Landscape of an Efferocytosis-Related Gene Signature in Bladder Cancer - Fuchun Zheng; Zhipeng Wang; Qianxi Dong; Sheng Li; Situ Xiong; Yuyang Yuan; Songhui Xu; Bin Fu (Biochemical Genetics, 2025)

Impact of SNP Variants in PON-1 or UGT1A1 on Iron Chelation Therapy Outcomes and Zinc Status in Thalassemia Major Patients - Meng-Yao Lu; Wan-Fu Tsai; Chang-Shiann Wu; Chien-Sheng Wang; Nailis Syifa; Mong-Liang Lu; Jiahn-Haur Liao; Wei J. Chen; Kai-Hsin Lin; Tzu-Hua Wu (Biological Trace Element Research, 2025)

Seismic Data Interpolation by AVO-Preserving Hyperbolic Radon Transform Using FISTA and Polynomial Fitting - Sheng-chao Wang; Han-feng Liu; De-fu Zhang; Hui Sun; Wei Zhang; Song-da Ji (Applied Geophysics, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Degradation of fluoranthene in aqueous solution and soil media by citric acid-enhanced FeS catalyzed sodium percarbonate - Xianxian Sheng; Meesam Ali; Ruoxuan Xu; Mudassir Habib; Xiang Zhang; Qian Sui; Rongbing Fu; Shuguang Lyu (Journal of Water Process Engineering, 2025)

Neurotoxicity of chronic nano-neodymium oxide exposure in zebrafish: Behavioral and molecular insights - Bao-Fu Zhang; Xing-Zhe Wu; Jin-Xia Wang; Yan-Ling Liao; Zi-Xin Cai; Yiyun Liu; De-Sheng Pei (Journal of Hazardous Materials, 2025)

Quality characteristics and structure-function relationships of peanut proteins from different phase sources by aqueous enzymatic extraction - Xin Guo; Wen-ye Xie; Hui Hu; Feng-ying Gu; Fu-sheng Chen; Xing-feng Guo; Bo Jiao; Qiang Wang (Food Chemistry, 2025)

Preparation of ginsenoside Re-ginseng protein nanoparticles and their ex vivo and in vivo studies - Yuanyuan Sheng; Weilin Yang; Yuxin Li; Wenxin Xia; Xueyan Fu (Food Bioscience, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

Characteristics and influence factors of ammonia emissions from light-duty vehicles under real-world driving conditions - Xian Wu; Han Jiang; Haiguang Zhao; Yitu Lai; Lei Zu; Yunjing Wang; Mingliang Fu; Sheng Su; Yan Ding (Fuel, 2025)

Physics-based and data-driven long-term evolution of a landslide: From inversion to prediction - Wenjie Du; Xiaodong Fu; Qian Sheng; Jian Chen; Yongqiang Zhou; Shaojie Zheng (Engineering Geology, 2025)

Physical rather than chemical protection determines soil organic carbon accumulation in a subtropical Chinese fir plantation treated by litter manipulation - Qiao Liu; Xiangjiang Liu; Zhigao Liao; Shengnan Wang; Junjie Huang; Yiqi Luo; Lifen Jiang; Geoff G. Wang; Huiming Wang; Fu-Sheng Chen (Plant and Soil, 2025)

Nutrient enrichment weakens the positive feedback of soil organic carbon decomposition to short-term warming in subtropical forests - Ming-Hui Meng; Chao Liang; Jin He; Zi-Yi Shi; Fu-Sheng Chen; Fang-Chao Wang; Xue-Li Jiang; Xiang-Min Fang (Plant and Soil, 2025)

Risk assessment of coastal dredging sediment plumes on the habitat of Indo-Pacific humpback dolphin (Sousa chinensis) - Chang He; Alessandro Stocchino; Zhen-Yu Yin; Francesco De Leo; Yin-Fu Jin; Xiang-Sheng Chen (Frontiers in Marine Science, 2025)
The Pearl River Estuary (PRE) and Hong Kong (HK) Waters are identified as two of the most important habitats worldwide for Indo-Pacific humpback dolphin ( Sousa chinensis ). However, the extremely rapid growth of coastal cities and near-shore reclamation lands posed great threats to delicate marine ecosystems and protected species. Dredging operations can exert non-negligible negative impacts on humpback dolphins, with high sediment concentrations standing out as a particularly significant threat. This study aims to apply a new risk assessment approach based on computational fluid dynamics (CFD) and unsupervised machine learning technique for quantitatively estimating the risk of high turbidity to marine mammals. As an extension, the risk to the natural habitat in PRE was statistically compared among five possible dredging locations according to HK reclamation projects. The results showed that sediment plumes could be enlarged quickly if dredging sites are close to places with high density of macro-vortices, such as the north corner of Lantau Island. In terms of temporal effects, dredging under scenarios with northeast wind has a higher probability of posing significant risks to dolphin habitats. In accordance with this strategy, reliable suggestions on the choice of construction location or period could be provided to the decision-makers before or during the coastal projects. The proposed strategy can also be flexibly extended to any coastal environment, serving as a valuable example for coastal and environmental management.

New horizon in particle physics: first observation of CP violation in baryon decays - Fu-Sheng Yu; Cai-Dian Lü (Science Bulletin, 2025)

Identification and functional analysis of an LTR retrotransposon insertion in CsPHYB associated with early senescence in cucumber (Cucumis sativus L.) - Hanqiang Liu; Kaihong Hu; Yuxuan Ma; Liting Fu; Zeqiang Huang; Zhihui Cheng; Yuyan Sheng; Dandan Li; Yupeng Pan (Plant Science, 2025)

Numerical investigation of aerated water entry by multiphase Riemann SPH method - Ke Zhao; Sheng-Fa Yang; Pei-Yin Yuan; Fu-Long Shi; Fu-Ren Ming (Ocean Engineering, 2025)

Enhanced manganese accumulation in female Populus cathayana via exogenous melatonin: A strategy for sex-based phytoremediation - Mingyue Fu; Yuan Yao; Ruixuan Liu; Zeyu Cai; Pei Wang; Fangyu Shen; Yutong He; Yao Chen; Sheng Zhang (Journal of Cleaner Production, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Physics-driven scenario deduction of the Xinhua Village Landslide disaster chain - Wenjie Du; Xiaodong Fu; Qian Sheng; Jian Chen; Yongqiang Zhou; Shaojie Zheng (Bulletin of Engineering Geology and the Environment, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Simulation study the PM oxidative regeneration procedures of diesel particulate filter based on a three-stage catalyst coating strategy - Wei Guan; Xiaolong Sheng; Changcheng Fu; Jinkai Gu; Yifang Zhou; Li Li; Zhiqing Zhang; Qiwei Wang; Mingzhang Pan (Journal of Environmental Chemical Engineering, 2025)

Saliency supervised masked autoencoder pretrained salient location mining network for remote sensing image salient object detection - Yuxiang Fu; Wei Fang; Victor S. Sheng (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Durability of an innovative self-healing geopolymer vertical barrier under dry-wet cycles - Qin-Pei Xue; Hong-Xin Chen; Shi-Jin Feng; Fu-Sheng Zha; Xiao-Lei Zhang (Engineering Geology, 2025)

Wide-bandgap perovskite solar cells with > 1.34 V Voc for all-perovskite tandems - Yunfei Li; Nannan Sun; Bo Feng; Wen Li; Zhengbo Cui; Wenxiao Zhang; Sheng Fu; Xiaodong Li; Junfeng Fang (Chemical Engineering Journal, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Single-cell dynamic RNA and glycosylation sequencing reveals the mechanism underlying the differentiation of pluripotent stem cells into hematopoietic stem cells - Wanyi Feng; Sheng Zeng; Donghui Liu; Wei Gong; Junjie Hu; Weihua Xu; Zhichao Ma; Shengmiao Fu; Xinping Chen (Human Cell, 2025)
Studying the mechanism of hematopoietic stem cells’ generation from induced pluripotent stem cells in vitro can be useful for understanding embryonic hematopoiesis, as well as for the application of related cell therapy. This study aimed to delineate the process of the differentiation of induced pluripotent stem cells into hematopoietic stem cells’ models and provide a theoretical basis and clinical value for the production of hematopoietic stem cells in vitro. We analyzed the differentiation model by single-cell dynamic transcriptome and glycosylation sequencing, which was divided into three differentiation stages based on the new‐to‐total RNA ratio and glycosylation level. Two differentiation fates were found in the pseudo-time, including hematopoietic development and other tissue development. Precursor hematopoietic cells with a high glycosylation level greatly expressed hematopoietic regulation and vascular endothelial genes, suggesting that glycosylation is associated with angiogenesis and hematopoietic regulation. The multiple differentiation events in the in vitro model are similar to those in hematopoietic development in vivo, including yolk sac hematopoiesis, cellular communication between non-potential hematopoietic subsets and potential hematopoietic subsets, gene expression, and temporal deviations in hematopoietic fate. Our study has revealed the similar hematopoiesis process in the differentiation model via single-cell dynamic RNA and glycosylation sequencing, which provides an important theoretical basis for the study of hematopoietic stem cell development.

The characteristics and distributions of alkaline-volcanic lithofacies of Fengcheng Formation in Mahu Sag, Junggar Basin - Zhi-qi Wu; Fu-sheng Yu; Jian Li; Qiang Liu; Xin Liu; Nai-xiang He (Applied Geophysics, 2025)

The characteristics of reservoir spaces and distribution of “sweet spots” in Fengcheng Formation of Mahu Sag, Junggar Basin - Zhi-qi Wu; Fu-sheng Yu; Jian Li; Qiang Liu; Xin Liu; Nai-xiang He (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Flammulina velutipes polysaccharides as an alternative cryoprotectant for frozen shrimp - Sheng Huang; Yan Cao; Yijia Zhang; Yin Fu; Erchao Li; Caifeng Jia (Journal of Food Engineering, 2025)

Heat transfer and energy storage characteristics of calcium carbonate particles in a countercurrent fluidized bed reactor - Jianhong Fu; Sheng Chen; Silong Chen; Mingyu Liu (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Dynamic response of slopes under near-field seismic excitation using the material point method - Wenjie Du; Xiaodong Fu; Qian Sheng; Jian Chen; Yongqiang Zhou; Shaojie Zheng (Computers and Geotechnics, 2025)

Surface display of aspartate ammonia-lyase from Lactobacillus paracasei on Pichia pastoris - Chen-Chi Chang; Yi-Hao Huang; Hua-Kun Fu; Kai-Wei Chang; Shih-Hsuan Chen; Yu-Ting Yu; Xin-Ying Lau; Jhih-Ying Ciou; He-Yuan Hsieh; Yung-Ju Chen; Lu-Sheng Hsieh (World Journal of Microbiology and Biotechnology, 2025)

Application of Unmanned Aerial Vehicle Remote Sensing on Dangerous Rock Mass Identification and Deformation Analysis: Case Study of a High-Steep Slope in an Open Pit Mine - Wenjie Du; Qian Sheng; Xiaodong Fu; Jian Chen; Jingyu Kang; Xin Pang; Daochun Wan; Wei Yuan (Journal of Earth Science, 2025)

Seafloor Sediment Classification Using Small-Sample Multi-Beam Data Based on Convolutional Neural Networks - Haibo Ma; Xianghua Lai; Taojun Hu; Xiaoming Fu; Xingwei Zhang; Sheng Song (Journal of Marine Science and Engineering, 2025)
Accurate, rapid, and automatic seafloor sediment classification represents a crucial challenge in marine sediment research. To address this, our study proposes a seafloor sediment classification method integrating convolutional neural networks (CNNs) with small-sample multi-beam backscatter data. We implemented four CNN architectures for classification—LeNet, AlexNet, GoogLeNet, and VGG—all achieving an overall accuracy exceeding 92%. To overcome the scarcity of seafloor sediment acoustic image data, we applied a deep convolutional generative adversarial network (DCGAN) for data augmentation, incorporating a de-normalization and anti-normalization module into the original DCGAN framework. Through comparative analysis of the generated versus original datasets using visual inspection and grayscale co-occurrence matrix methods, we substantially enhanced the similarity between synthetic and authentic images. Subsequent model training using the augmented dataset demonstrated improved classification performance across all architectures: LeNet showed a 1.88% accuracy increase, AlexNet an increase of 1.06%, GoogLeNet an increase of 2.59%, and VGG16 achieved a 2.97% improvement.

Revealing the mobilization and age of estuarine dissolved organic matter during floods using radiocarbon and molecular fingerprints - Zhao Liang Chen; Yuanbi Yi; Ruanhong Cai; Zhe-Xuan Zhang; Wenzhao Liang; Wenjing Fu; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; et al. (Water Research, 2025)

Decreased stability of soil dissolved organic matter under disturbance of periodic flooding and drying in reservoir drawdown area - Shengman Zhang; Yuchun Wang; Ming Sheng; Xueping Chen; Ziyuan Zhang; Shanze Li; Yong Qin; Pingqing Fu; Fushun Wang (Science of The Total Environment, 2025)

Determining representative elementary volume for hydraulic conductivity of fractured rock masses: Comparative analytical and numerical studies - Tai-Sheng Liou; Jia-Jing Lin; Po-Kai Chen; En-Chao Yeh; Fu-Shu Jeng; Tai-Tien Wang (Engineering Geology, 2025)

Evolution of bearing capacity and macroelement modelling for suction caisson foundations in sand considering local scour - Zhuang Jin; Yin-Fu Jin; Zhen-Yu Yin; Xiang-Sheng Chen (Computers and Geotechnics, 2025)

An advanced numerical approach for flowslides in informal landfills considering the softening and state transition of MSW - Qi-Teng Zheng; An-Zheng Li; Shi-Jin Feng; Fu-Sheng Zha; Yong Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Exploring water quality variations and biofilm growth in a drinking water distribution system via a biofilm annular reactor series system and predictive modelling of residual chlorine - Zhong Sheng Tai; Yuanpeng Sun; Carl Angelo Dulatre Medriano; Yuyao Fu; Yuyang Jiang; Fengyuan Lei; Ke Liu; Tianyu Yan; Lee Jie Xin Eve; Sung Woo Bae; Quek Puay Hoon Elaine; Phen Wei Chue; et al. (Chemosphere, 2025)

Effects of dietary resveratrol supplementation on the growth performance, physiological health, transcriptomic response, and intestinal microflora of Litopenaeus vannamei - Zhibin Fu; Jian Chen; Hang Yuan; Yudong Zheng; Gongyu Li; Sheng Ke; Shuang Zhang; Lili Shi (Aquaculture, 2025)

Latest research progress on anti-microbial effects, mechanisms of action, and product developments of dietary flavonoids: A systematic literature review - Jincan Luo; Jinhai Luo; Zhili Sheng; Zhonghao Fang; Yu Fu; Nannan Wang; Bao Yang; Baojun Xu (Trends in Food Science & Technology, 2025)

Applications of high-gravity technologies in industrial sewage purification: A review - Bin Huang; Sheng-Jie Feng; Hao Chen; Wei Zhang; Cheng Fu (Process Safety and Environmental Protection, 2025)

Gentidelasides A−G: Loganin derivatives from Gentiana delavayi with reducing Aβ secretion via suppressing BACE1 expression - Hai-Hui Guo; Chun-Xu Li; Min Yang; Feng-Feng Li; Hui-Yun Yang; Ming Yin; Jia-Peng Wang; Fu-Sheng Wang (Phytochemistry, 2025)

A NIR fluorescent probe based on carbamoyl oxime with high specificity for detecting ferrous ions in food and in vivo - Caiyun Liu; Tingyi Yan; Tingting Fu; Kun Wang; Xiaodi Rong; Xueting Liu; Yao Wang; Xinyu Cai; Wenlong Sheng; Baocun Zhu (Food Research International, 2025)

Low-Temperature fabrication of CsPbI3@PVA films for Ultra-Stable Down-Conversion white Light-Emitting Diodes: From molecular interactions to phase stability - Hao Zhang; Jinju Zheng; Hui Fu; Jialiang Jiang; Deliu Ou; Jinliang Jiang; Pinjing Luo; Jialong Zhao; Roman Romashko; Aleksandr Kuchmizhak; Alexey Zhizhchenko; Sheng Cao; et al. (Chemical Engineering Journal, 2025)

Unraveling the role of oxygen vacancies in enhancing the SO2-resistance of α-MnO2 towards elemental mercury removal - Qian Yu; Fei Lai; Shiwei Sheng; Yujia Wang; Bo Yuan; Dong Fu (Chemical Engineering Journal, 2025)

Tectono-sequence evolution of an extensional strike-slip composite basin, a case study of the Miaoxi'nan sub-sag in the eastern Bohai Bay Basin - Sheng Fu; Haifeng Yang; Lijun Song; Wei Zhou; Jiawang Ge; Yanqin Guo (Marine and Petroleum Geology, 2025)

Dual regulation of As release and soil environment by Fe(Ⅱ) assisted steel slag and coal fly ash: Effects and potential mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Hazardous Materials, 2025)

Valorization of corn stalk hydrochar by similar steam explosion during hydrothermal carbonization: Structure evolution and pyrolysis behavior - Zhenfei Liu; Fang Wang; Hongyue Fu; Yuwan Sheng; Xiuli Shen; Weiming Yi; Deli Zhang (Journal of Cleaner Production, 2025)

Enhancing rainwater harvesting efficiency in karst terrains: The role of road intercepted soil-epikarst lateral flow - Zhiyong Fu; Peining Liang; Hamid M. Behzad; Rongjie Fang; Sheng Wang; Jie Zhao; Hongsong Chen (Journal of Environmental Management, 2025)

Structural characteristics of areca nut seed neutral polysaccharide and its impact on gut microbiota from human feces - Mengfan Zhang; Haining Zhuang; Xiaowei Zhang; Xiaoyu Wang; Xia Fu; Sheng Chen; Lingyun Yao; Huatian Wang; Min Sun; Chuang Yu; Heng Yue; Tao Feng (Food Hydrocolloids, 2025)

A Python toolkit for integrating geographic information system into regulatory dispersion models for refined pollution modeling - Haobing Liu; Pengfei Gao; Sheng Xiang; Hong Zhu; Jia Chen; Qingyan Fu (Environmental Modelling & Software, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

The impact of leak gap size and position on surgical mask performance of source control: A numerical study - Feifan He; Jialin Wu; Yayun Li; Ming Fu; Sheng He; Wenguo Weng (Building and Environment, 2025)

Intrathecal Fumagillin Alleviates Chronic Neuropathy-Induced Nociceptive Sensitization and Modulates Spinal Astrocyte-Neuronal Glycolytic and Angiogenic Proteins - Zhi-Hong Wen; Zong-Sheng Wu; Hao-Jung Cheng; Shi-Ying Huang; Shih-Hsuan Tang; Wei-Nung Teng; Fu-Wei Su; Nan-Fu Chen; Chun-Sung Sung (Molecular Neurobiology, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

The causal effect of losing irrigated water on farmland prices - Hung-Hao Chang; Brian Lee; Sheng-Fu Tsai (Paddy and Water Environment, 2025)

Whole-genome mutagenesis of whiteleg shrimp (Litopenaeus vannamei) by ARTP and analysis of its mutational characteristics - Qiang Fu; Jingxin Zhou; Sheng Luan; Kun Luo; Baolong Chen; Jiawang Cao; Xupeng Li; Qun Xing; Jie Kong; Xianhong Meng (Aquaculture, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

The pivotal role of arbuscular mycorrhizal fungi in enhancing plant biomass and nutrient availability under drought stress conditions: A global meta-analysis - Fawad Zaman; Muhammad Umair Hassan; Wajid Ali Khattak; Ahmad Ali; Mohamed F. Awad; Fu-Sheng Chen (Science of The Total Environment, 2024)

The role of deep learning in aortic aneurysm segmentation and detection from CT scans: A systematic review and meta-analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Next Research, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Biogeochemical process governing cadmium availability in sediments of typical coastal wetlands driven by drying-wetting alternation - Cheng-Cheng Jiang; Guang-Hui Yu; Xiao-Jie Zhou; Fu-Sheng Sun; Cong-Qiang Liu (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Fe-MOF derived Fe3O4/C-based hydrogel for efficient solar-driven photothermal evaporation - You Zhou; Lei Xu; Sheng-Jie Han; Cai-Hua Liu; Yi-Bin Li; Ming-Lai Fu; Baoling Yuan (Desalination, 2024)

Functional characterization of Arabidopsis hydroxynitrile lyase in response to abiotic stress and the regulation of flowering time - Lei Xue; Duo Bu; Jiangyan Fu; Zhe Zhou; Meng Gao; Ren Wang; Sheng Xu (Molecular Biology Reports, 2024)

Improvements in source apportionment of multiple time-resolved PM2.5 inorganic and organic speciation measurements using constrained Positive Matrix Factorization - Chun-Sheng Huang; Yi-Hsien Liu; Ho-Tang Liao; Chia-Yang Chen; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Characterizing rapid infiltration processes on complex hillslopes: Insights from soil moisture response to rainfall events - Jun Zhang; Sheng Wang; Zhiyong Fu; Kelin Wang; Hongsong Chen (Journal of Hydrology, 2024)

Finite difference solution for contaminant transport through a GCL composite cutoff wall-aquifer system considering semipermeable membrane effect - He-Fu Pu; Sheng-Yi Deng; Ming Min; Yong-Wei Zhou (Journal of Hydrology, 2024)

Corrigendum to “Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region” [J. Clean. Prod. 479 (2024) 144006] - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Spatial heterogeneity of ecosystem service bundles and the driving factors in the Beijing-Tianjin-Hebei region - Qing Li; Dan Li; Jinfeng Wang; Sheng Wang; Rende Wang; Gang Fu; Yixiao Yuan; Zhenhua Zheng (Journal of Cleaner Production, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Molecular cloning and functional characterization of eight galectin genes from Takifugu obscurus - Ying Huang; Sheng-Hao Du; Li-Fan Cui; Fu-Hui Jiang; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Anti-seepage performance and oxygen barrier performance of the three-layered landfill cover system comprising neutralized slag under extreme climate conditions - Ming Min; He-Fu Pu; Xiao He; Sheng-Yi Deng (Engineering Geology, 2024)

A semi-empirical parameter predicting the sensitivity of energetic materials from external pressure - Zhi-Xin Bai; Wei Zeng; Cheng-Lu Jiang; Fu-Sheng Liu; Zheng-Tang Liu; Qi-Jun Liu (Chemical Engineering Journal, 2024)

A point-of-care testing strip based on a rationally designed antigen and antibody for fast and reliable Diquat poisoning detection: Ready for clinical application - Shun Zhang; Guanyan Fu; Weijing Yi; Jiahui Zhou; Wenbin Liang; Wanjiang Zhao; Tian Zhang; Gen Zhang; Jing Zhang; Huiling Li; Huifang Yan; Banghua Wu; et al. (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Remediation of As, Sb, and Pb co-contaminated mining soils by using Fe/C based solid wastes: Synergistic effects and field applications - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Wen Ni; Siqi Zhang; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

A low-cost salt-tolerant solar evaporator prepared from graphite in spent LIBs for high efficiency seawater desalination - Sheng-Jie Han; Lei Xu; Zhen-Yu Wang; Cai-Hua Liu; Ming-Lai Fu; Baoling Yuan (Chemical Engineering Journal, 2024)

Remediation of multiple heavy metals contaminated soils by Mn and Fe-added solid wastes: Effect and mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Simultaneous removal of Cd(II) and phosphate by nanoscale zero-valent iron from solution: Co-sorption and implication of corrosion - Haoyang Fu; Jie Sheng; Chenliu Tang; Wei-xian Zhang; Lan Ling (Chemosphere, 2024)

Metabolic and process engineering of Clostridium tyrobutyricum for efficient hydrogen production from sugarcane molasses - Hongxin Fu; Die Yang; Xin Li; Xiaolong Guo; Yongzhang Mo; Sheng Wang; Jufang Wang (Fuel, 2024)

Long-term non-flooded cultivation with straw return maintains rice yield by increasing soil pH and soil quality in acidic soil - Jingjie Zhou; Sheng Tang; Wankun Pan; Xiu Liu; Kefeng Han; Linlin Si; Qingxu Ma; Xiali Mao; Haoran Fu; Lianghuan Wu (European Journal of Agronomy, 2024)

Inefficient burial of terrestrial organic carbon in deltas - Yonggui Yu; Jaap H. Nienhuis; Zhengquan Yao; Marcel van der Perk; Bin Zhao; Shuqing Qiao; Xuefa Shi; Gabriel Cardenas-Belleza; Sheng Fu; Francien Peterse; Yazhi Bai; Hans Middelkoop (Earth and Planetary Science Letters, 2024)

Detection of dual-methylated BRCA1/BRCA2 cell-free DNA for ovarian cancer on an aptamer-based integrated microfluidic system - Chih-Hung Wang; Yang-Sheng Shao; Keng-Fu Hsu; Gwo-Bin Lee (Chemical Engineering Journal, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Integrating spatially distributed data into Positive Matrix Factorization to identify the hotspots of local emission sources - Chun-Sheng Huang; Ho-Tang Liao; Chang-Fu Wu (Atmospheric Research, 2024)

Multi-dimensional microfluidic paper-based analytical devices (μPADs) for noninvasive testing: A review of structural design and applications - Ting Chen; Ce Sun; Syed Comail Abbas; Nur Alam; Sheng Qiang; Xiuzhi Tian; Chenglong Fu; Hui Zhang; Yuanyuan Xia; Liu Liu; Yonghao Ni; Xue Jiang (Analytica Chimica Acta, 2024)

Innovative strategy for the effective utilization of coal waste slag in the Fenton-like process for the degradation of trichloroethylene - Mudassir Habib; Tehreem Ayaz; Meesam Ali; Muhammad Zeeshan; Xianxian Sheng; Rongbing Fu; Siraj Ullah; Shuguang Lyu (Journal of Environmental Management, 2024)

Degradation behaviors of Nabumetone and its metabolite during UV/monochloramine process: Experimental and theoretical study - Xiang Tu; Yunsong Bai; Qing Fu; Sheng Chang; Kunfeng Zhang; Yang Pan; Ruiyang Xiao; Yifu Fu; Qi Zhang (Journal of Environmental Sciences, 2024)

Quantitative assessment of the impact factors upon remediation performance of the PRB technique in conjunction with pumping/recharge - Han Xiao; Yu Yang; Xiangjian Xu; Sheng Deng; Xu Han; Fu Xia; Yonghai Jiang (Groundwater for Sustainable Development, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Deep Learning Models for Aorta Segmentation in Computed Tomography Images: A Systematic Review And Meta-Analysis - Ting-Wei Wang; Yun-Hsuan Tzeng; Jia-Sheng Hong; Ho-Ren Liu; Kuan-Ting Wu; Hao-Neng Fu; Yung-Tsai Lee; Wei-Hsian Yin; Yu-Te Wu (Journal of Medical and Biological Engineering, 2024)
Purpose This systematic review and meta-analysis was conducted to evaluate the usefulness of deep learning (DL) models for aorta segmentation in computed tomography (CT) images. Methods Adhering to 2020 PRISMA guidelines, we systematically searched PubMed, Embase, and Web of Science for studies published up to March 13, 2024, that used DL models for aorta segmentation in adults’ chest CT images. We excluded studies that did not use DL models, involved nonhuman subjects or aortic diseases (aneurysms and dissections), or lacked essential data for meta-analysis. Segmentation performance was evaluated primarily in terms of Dice scores. Subgroup analyses were performed to identify variations related to geographical location and methodology. Results Our review of 16 studies indicated that DL models achieve high segmentation accuracy, with a pooled Dice score of 96%. We further noted geographical variations in model performance but no significant publication bias, according to the Egger test. Conclusion DL models facilitate aorta segmentation in CT images, and they can therefore guide accurate, efficient, and standardized diagnosis and treatment planning for cardiovascular diseases. Future studies should address the current challenges to enhance model generalizability and evaluate clinical benefits and thus expand the application of DL models in clinical practice.

Perturbation algorithm for refueling reactivity coefficient in the pebble-bed high temperature reactor - Zhongkai Sheng; Bing Xia; Ding She; Fu Li; Zuoyi Zhang (Annals of Nuclear Energy, 2024)

Parotid Gland Segmentation Using Purely Transformer-Based U-Shaped Network and Multimodal MRI - Zi’an Xu; Yin Dai; Fayu Liu; Siqi Li; Sheng Liu; Lifu Shi; Jun Fu (Annals of Biomedical Engineering, 2024)

Transient analytical solution for coupled water–gas transport in unsaturated soil cover of landfill - He-Fu Pu; Ming Min; Sheng-Yi Deng; Xiao-Jun Wen; Jun Xu (Journal of Hydrology, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Severe flood modulates the sources and age of dissolved organic carbon in the Yangtze River Estuary - Zhao Liang Chen; Yuanbi Yi; Wenjing Fu; Wenzhao Liang; Penghui Li; Kai Wang; Lixin Zhang; Kejun Dong; Si-Liang Li; Sheng Xu; Ding He (Environmental Research, 2024)

FPS-U2Net: Combining U2Net and multi-level aggregation architecture for fire point segmentation in remote sensing images - Wei Fang; Yuxiang Fu; Victor S. Sheng (Computers & Geosciences, 2024)

Divergent responses of soil microbial community to long-term nitrogen and phosphorus additions in a subtropical Chinese fir plantation - Fangchao Wang; Qiao Liu; Xiaofei Hu; Xiang-Min Fang; Shengnan Wang; Fu-Sheng Chen (CATENA, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Alleviating binary toxicity of polystyrene nanoplastics and atrazine to Chlorella vulgaris through humic acid interaction: Long-term toxicity using environmentally relevant concentrations - Mehdi Khoshnamvand; Dongmei You; Yafang Xie; Yixiao Feng; Marriya Sultan; De-Sheng Pei; Ailing Fu (Chemosphere, 2024)

Presence of humic acid in the environment holds promise as a potential mitigating factor for the joint toxicity of polystyrene nanoplastics and herbicide atrazine to Chlorella vulgaris: 96-H acute toxicity - Mehdi Khoshnamvand; Dongmei You; Yafang Xie; Yixiao Feng; Marriya Sultan; Xingyi Wei; Jingli Li; Ailing Fu; De-Sheng Pei (Chemosphere, 2024)

SLC11A1 promotes kidney renal clear cell carcinoma (KIRC) progression by remodeling the tumor microenvironment - Ding Wu; Yulin Zhou; Xiuquan Shi; Xiaoming Yi; Zhengcheng Sheng; Li Fan; Jingping Ge; Wen Cheng; Wenquan Zhou; Haowei He; Dian Fu (Toxicology and Applied Pharmacology, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Application of sulfidated nano zero-valent iron to enhance fluoranthene degradation by Fe(III) activated sodium percarbonate process in aqueous and soil media - Xianxian Sheng; Yulong Liu; Meesam Ali; Mudassir Habib; Rongbing Fu; Shuguang Lyu (Journal of Environmental Chemical Engineering, 2024)

Utilizing waste corn straw to photodegrade methyl orange and methylene blue: Photothermal effect of biochar enhances photodegradation efficiency - Peng Jiang; Li Zhou; Yongfen Han; Wei Fu; Sheng Su; Maoqin Zeng (Journal of Environmental Chemical Engineering, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Were oxygen isotopes of hydrothermally altered minerals just elevated by the 18O-enriched water? Theoretical inversion with thermodynamics and kinetics - Chun-Sheng Wei; Zi-Fu Zhao (Mineralogy and Petrology, 2024)

Analysis of historical evolution characteristics and collapse process on July 18, 2023, of a dangerous rock mass at Guanyinyan in Baoxing County, Sichuan Province, China - Xing Wang; Xiaodong Fu; Kai Wu; Haifeng Ding; Wenjie Du; Qian Sheng; Jian Chen (Landslides, 2024)

Exploring the effects of different fertilizer application durations on the functional microbial profiles of soil carbon and nitrogen cycling by using metagenomics in Paulownia plantations in a subtropical zone - Sen Liu; Xia Li; Yujia Fu; Peng Li; Jie Qiao; Hui Li; Lichao Wu; Baoping Wang; Sheng Lu (European Journal of Forest Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Soil amendments reduce CH4 and CO2 but increase N2O and NH3 emissions in saline-alkali paddy fields - Hu Cui; Hui Zhu; Fu-Man Zhang; Xin-Yi Wang; Sheng-Nan Hou; Wei-Dong Feng (Science of The Total Environment, 2024)

Enhanced home-field advantage in deep soil organic carbon decomposition: Insights from soil transplantation in subtropical forests - Kuan Liang; Yong Lin; Tiantian Zheng; Fangchao Wang; Yuandong Cheng; Shennan Wang; Chao Liang; Fu-Sheng Chen (Science of The Total Environment, 2024)

Heavy metals in centralized drinking water sources of the Yangtze River: A comprehensive study from a basin-wide perspective - Kunfeng Zhang; Sheng Chang; Xiang Tu; Enrui Wang; Yanling Yu; Jianli Liu; Lu Wang; Qing Fu (Journal of Hazardous Materials, 2024)

Assessing the health risks of heavy metals and seasonal minerals fluctuations in Camellia sinensis cultivars during their growth seasons - Fawad Zaman; Wajid Ali Khattak; Muhammad Ihtisham; Muhammad Ilyas; Ahmad Ali; Abbas Ali; Haroon Khan; Khalid Ali Khan; Dejiang Ni; Hua Zhao; Fu-Sheng Chen (Food and Chemical Toxicology, 2024)

Ceria nanoparticles: biomedical applications and toxicity - Xiaoxuan Fu; Peng Li; Xi Chen; Yuanyuan Ma; Rong Wang; Wenxuan Ji; Jiakuo Gu; Bowen Sheng; Yizhou Wang; Zhuhong Zhang (Journal of Zhejiang University-SCIENCE B, 2024)

Semi-automatic identification of rock discontinuity orientation based on 3D point clouds and its engineering application - Jingyu Kang; Xiaodong Fu; Qian Sheng; Yunfeng Ge; Jian Chen; Haibin Wang (Bulletin of Engineering Geology and the Environment, 2024)

Predictive Model to Identify the Long Time Survivor in Patients with Glioblastoma: A Cohort Study Integrating Machine Learning Algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Yun-Long Sheng; Guang-Yu Wang; Fu-Quan Zhang; Xin Lian (Journal of Molecular Neuroscience, 2024)

A review of solid wastes-based stabilizers for remediating heavy metals co-contaminated soil: Applications and challenges - Yuliang Zhang; Pingfeng Fu; Wen Ni; Siqi Zhang; Sheng Li; Wei Deng; Wentao Hu; Jia Li; Fuyun Pei; Linfeng Du; Yueling Wang (Science of The Total Environment, 2024)

Novel application of high temperature solution growth method in simultaneously preparing SiC/Ti3SiC2/TiC using photovoltaic Si waste and Ti-bearing blast furnace slag - Sheng Pang; Hao Wang; Guoyu Qian; Yiwei Sun; Wenlong Fu; Jijun Lu; Zhilin Sheng; Zhi Wang (Journal of Cleaner Production, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

Catalytic co-pyrolysis of coffee grounds and polyethylene: A comparison of HZSM-5 and HY - Jiawei Fu; Sen Lin; Bin Cai; Jiayu Liang; Zhibin Chen; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Chunxiao Yang; Yao He; Shuiyu Sun; Jingyong Liu (Fuel, 2024)

Cationic cellulose nanofibers/chitosan auxiliary-dominated win-win strategy for paper yarn with superior color and physical performances - Xiaohui Guo; Rendang Yang; Yang Wang; Shuzhen Ni; Chen Cheng; Danning Fu; Jie Sheng (Carbohydrate Polymers, 2024)

Soil thickness influences the control effect of micro-topography on subsurface runoff generation in the karst hillslope critical zone - Jun Zhang; Sheng Wang; Zhiyong Fu; Fa Wang; Kelin Wang; Hongsong Chen (CATENA, 2024)

Development and Application of an Industrial Wastewater Profile Database - Pei-Yuan Hsieh; Gen-Shuh Wang; Wen-Huey Mi; Chun-Sheng Huang; Chang-Fu Wu (Water, Air, & Soil Pollution, 2024)

LiCOI1 mediates the biosynthesis of monoterpenes induced by methyl jasmonate in Lilium ‘Siberia’ - Zhuo Leng; Ying-Ying Li; Yu-Chen Fu; Jing Wu; Ping-Sheng Leng; Zeng-Hui Hu (Horticulture, Environment, and Biotechnology, 2024)

Towards standardizing automated image analysis with artificial intelligence for biodiversity - Peng Zhou; Yu-Xin Bu; Ge-Yi Fu; Chun-Sheng Wang; Xue-Wei Xu; Xiaoyong Pan (Frontiers in Marine Science, 2024)

Spatiotemporal successions of N, S, C, Fe, and As cycling genes in groundwater of a wetland ecosystem: Enhanced heterogeneity in wet season - Xianglong Chen; Yizhi Sheng; Guangcai Wang; Pengpeng Zhou; Fu Liao; Hairu Mao; Hongyu Zhang; Zhiyuan Qiao; Yuquan Wei (Water Research, 2024)

Root acquisitive traits mirror the functional modules of root-associated fungi - Gaigai Ding; Wenjing Zeng; Lijuan Sun; Fu-Sheng Chen; Yun Lyu; Jin Xu; Tao Yan; Huimin Wang; Zeqing Ma (Soil Biology and Biochemistry, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Emplacement and ore potential of the Permian Pobei mafic–ultramafic complex, NE Tarim, NW China - Sheng-Hong Yang; Mei-Fu Zhou; Christina Yan Wang; Changyi Jiang (Journal of Asian Earth Sciences, 2024)

Unusual weakening trend of the East Asian winter monsoon during MIS 8 revealed by Chinese loess deposits and its implications for ice age dynamics - Qingzhen Hao; Shuzhen Peng; Xinbo Gao; Slobodan B. Marković; Sheng-Hua Li; Junjie Zhang; Fengjiang Li; Long Han; Yu Fu; Xuechao Wu; Luo Wang; Bing Xu; et al. (Global and Planetary Change, 2024)

Propyl gallate exposure affects the mouse 2-cell stage embryonic development through inducing oxidative stress and autophagy - Sheng-Ji Yang; Fu-Yi Yang; Yi-Nuo Zou; Yong-Sheng Wang; Zhi-Ming Ding; Li-Dan Zhang; Xu Zhou; Ming Liu; Ze-Qun Duan; Li-Jun Huo (Food and Chemical Toxicology, 2024)

Synergistic binding mechanisms of co-contaminants in soil profiles: Influence of iron-bearing minerals and microbial communities - Fu-Sheng Sun; Miao-Miao Wang; Xiang-Yang Zhao; Qiao-Yun Huang; Cong-Qiang Liu; Guang-Hui Yu (Environmental Pollution, 2024)

Zero valent iron and amorphous boron-assisted nano calcium peroxide/Fe(III) system for naphthalene degradation: Efficient performance and diverse mechanisms - Yulong Liu; Xianxian Sheng; Yong Sun; Mudassir Habib; Qian Sui; Rongbing Fu; Shuguang Lyu (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

PPARβ/δ-ANGPTL4 axis mediates the promotion of mono-2-ethylhexyl phthalic acid on MYCN-amplified neuroblastoma development - Yiyun Liu; Naima Hamid; Rakia Manzoor; Bao-Fu Zhang; Yan-Ling Liao; Jin-Xia Wang; De-Sheng Pei (Science of The Total Environment, 2024)

A landslide dating framework using a combination of Sentinel-1 SAR and -2 optical imagery - Sheng Fu; Steven M. de Jong; Xuejiao Hou; Job de Vries; Axel Deijns; Tjalling de Haas (Engineering Geology, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Effects of tillage practices on soil organic carbon, microbial community and necromass in a double rice cropping system - Jian-Ying Qi; Xiang-Bin Yao; Xue-Chan Zhang; Mei-Yi Fan; Jian-Fu Xue; Jun-Li Cao; Ahmad Latif Virk; Sheng-Gang Pan; Xiang-Ru Tang (Applied Soil Ecology, 2024)

Investigating enzyme kinetics and fluorescence sensing strategy of CRISPR/Cas12a for foodborne pathogenic bacteria - XuRan Fu; JiaDi Sun; Bingqian Yu; Yongli Ye; Lina Sheng; Jian Ji; Jiayu Zheng; Minghong Fan; Jingdong Shao; XiuLan Sun (Analytica Chimica Acta, 2024)

Reconstruction of microcontinents during the assembly of Rodinia: A case study from the Central Tianshan Block - Lin-Xi Wang; Hu Huang; Ming-Cai Hou; Benjamin Kneller; Fu-Hao Xiong; Hong-Wei Luo; Sheng-Xian Zhu (Precambrian Research, 2024)

Co-evolution among soil thickness, epikarst weathering degree, and runoff characteristics on a subtropical karst hillslope - Sheng Wang; Yan Yan; Yinjun Zhao; Zhiyong Fu; Hongsong Chen (Journal of Hydrology, 2024)

Iron-catalyzed sulfur alkylation of sulfenamides with in situ-generated 2,2,2-trifluorodiazoethane - Xianda Wu; Minghong Chen; Shuiyun Zheng; Fu-Sheng He; Jie Wu (Journal of Fluorine Chemistry, 2024)

Energy management for proton exchange membrane fuel cell-lithium battery hybrid power systems based on real-time prediction and optimization under multimodal information - Linghong Zeng; Jun Fu; Chuang Sheng; Beijia Li; Ziang Guo; Qian Xiang; Jingjing Wang; Xinkai Shan; Xiaowei Fu; Zhonghua Deng; Zhuo Wang; Xi Li (Journal of Cleaner Production, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Scalable and room-temperature preparation of Cs2HfCl6 double perovskites with recorded photoluminescence efficiency and robust stability - Jialiang Jiang; Jinju Zheng; Hui Fu; Hao Zhang; Deliu Ou; Qiaochu Chen; Kai Wang; Sheng Cao; Jialong Zhao; Zhentao Du; Weiyou Yang (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Limits on scalar-induced gravitational waves from the stochastic background by pulsar timing array observations - Yi-Fu Cai; Xin-Chen He; Xiao-Han Ma; Sheng-Feng Yan; Guan-Wen Yuan (Science Bulletin, 2023)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

Deterministic factors modulating assembly of groundwater microbial community in a nitrogen-contaminated and hydraulically-connected river-lake-floodplain ecosystem - Zhiyuan Qiao; Yizhi Sheng; Guangcai Wang; Xianglong Chen; Fu Liao; Hairu Mao; Hongyu Zhang; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Journal of Environmental Management, 2023)

Study on Macroscopic Mechanical Behavior and Meso-failure Evolution of Gabbro of Different Particle Sizes - Haifeng Ding; Xiaodong Fu; Qian Sheng; Jian Chen; Chengzeng Yan; Kaiwei Tian; Bo Hu (Rock Mechanics and Rock Engineering, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Canagliflozin ameliorates high glucose-induced apoptosis in NRK-52E cells via inhibiting oxidative stress and activating AMPK/mTOR-mediated autophagy - Hong Liu; Weidong Chen; Sheng Wan; Ye Chen; Mengjing Fu; Zengsi Wang; Fei Xiong; Yanmin Zhang (Molecular Biology Reports, 2023)

Failure history, mechanism, and recent run-out reproduction of the Xinhua Village landslide triggered by the 2022 Ms 6.1 Lushan earthquake - Wenjie Du; Kai Wu; Xiaodong Fu; Qian Sheng; Jian Chen; Xing Wang (Landslides, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Long-term application of controlled-release fertilizer enhances rice production and soil quality under non-flooded plastic film mulching cultivation conditions - Jingjie Zhou; Sheng Tang; Wankun Pan; Meng Xu; Xiu Liu; Liang Ni; Xiali Mao; Tao Sun; Haoran Fu; Kefeng Han; Qingxu Ma; Lianghuan Wu (Agriculture, Ecosystems & Environment, 2023)

Andrographolide inhibits the activation of spinal microglia and ameliorates mechanical allodynia - Dan Wang; Yongjian Zheng; Junjing Xie; Wenwen Yu; Zhongteng Lu; Wenping Zhang; Yanling Hu; Jianyuan Fu; Qing Sheng; Zhengbing Lv (Metabolic Brain Disease, 2023)

The effect of polycentric urban spatial structure on PM2.5: An empirical study of China - Sheng Zheng; Yukuan Huang; Yuyuan Fu (Sustainable Cities and Society, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Discovery and identification of a novel canine coronavirus causing a diarrhea outbreak in Vulpes - Yuting Liu; Yao Deng; Sheng Niu; Na Zhu; Jingdong Song; Xiaoshuang Zhang; Weiting Su; Wenhui Nie; Roujian Lu; David M. Irwin; George Fu Gao; Wenling Wang; et al. (Science Bulletin, 2023)

Stability evaluation of salt cavern hydrogen storage and optimization of operating parameters under high frequency injection production - De-Peng Li; Wei Liu; Pan Fu; Lin Li; Fan-Sheng Ban; Qi-Hang Li; Jin-Yang Fan; De-Yi Jiang; Zhi-Xin Zhang (Gas Science and Engineering, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Deep utilization of salinity gradient energy between concentrated seawater and river water by multi-stage reverse electrodialysis - Zhi-Yuan Guo; Wei-Zhe Cui; Zhi-Yong Ji; Kaniki Tumba; Jing Wang; Liu-Jia Fu; Zhao-Xiang Zhang; Jie Liu; Ying-Ying Zhao; Zhong-De Zhang; Jun-Sheng Yuan (Desalination, 2023)

CFD-DEM investigation of flow and heat transfer characteristics in a directly irradiated fluidized bed - Xiaochen Zhou; Jianhong Fu; Sheng Chen (Chemical Engineering Journal, 2023)

Spatial pattern of hydrological and erosion behaviour along a dolomite hillslope in Southwest China - Qingmei Meng; Sheng Wang; Zhiyong Fu; Yusong Deng; Hongsong Chen (CATENA, 2023)

Design and verification of a wearable wireless 64-channel high-resolution EEG acquisition system with wi-fi transmission - Chin-Teng Lin; Yuhling Wang; Sheng-Fu Chen; Kuan-Chih Huang; Lun-De Liao (Medical & Biological Engineering & Computing, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Microplastics in the soil environment: Focusing on the sources, its transformation and change in morphology - Junyu Zhu; Guowen Dong; Fu Feng; Jing Ye; Ching-Hua Liao; Chih-Hung Wu; Sheng-Chung Chen (Science of The Total Environment, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Coloration of cotton fibers with inorganic pigments using a transient high-temperature technology - Qimeng Zhu; Zhuan Fu; Liangjun Xia; Xiaofeng Wang; Zhaozixuan Zhou; Dan Sheng; Xinjie Wei; Junyao Gong; Sijie Zhou; Wenbin Li; Chunhua Zhang (Journal of Cleaner Production, 2023)

The effect of glycerol additive on high value-added chemicals from tobacco waste pyrolysis - Jia-hao Wang; Xian-jie Zhang; Qian Xia; Shui yang Fang; An-fu Hu; Jun Wen; Sheng-jun Zhou; Wen-xian Chen; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2023)

Risk-based irrigation decision-making for the Shihmen Reservoir Irrigation District of Taiwan - Sheng-Fu Tsai; Dong-Hong Wu; Gwo-Hsing Yu; Ke-Sheng Cheng (Paddy and Water Environment, 2023)

Novel protection systems for the improvement in soil and water stability of expansive soil slopes - Shao-kun Ma; Ben-fu He; Min Ma; Zhen Huang; Sheng-jia Chen; Huan Yue (Journal of Mountain Science, 2023)

Molecular characterization, spatiotemporal expression patterns of fatty acid elongase (elovl8) gene, and its transcription changes in response to different diet stimuli in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Xiu-Ying Wei; Wei Qin; Chuan-Jie Qin; Qiong Shi; Sheng-Tao Guo; Panita Prathomya; Shi-Yong Zhang; Peng Fu; Wei Hu; Han-Wen Yuan; Zheng-Yong Wen (Frontiers in Marine Science, 2023)
Elongase of very long-chain fatty acid 8 (Elovl8) is a new member identified in the Elovl family that is involved in the synthesis of highly unsaturated fatty acids (HUFAs). However, the evolutionary and physiological roles of this enzyme are still largely unknown. In the present study, the elovl8 gene was identified and characterized from yellow catfish Pelteobagrus fulvidraco , and then its evolutionary and molecular characteristics as well as transcriptional changes in response to various nutritional status were determined. Results showed that the open reading frame (ORF) of elovl8 was 795 bp in length, encoding a protein of 264 amino acids. Multiple sequences alignment showed that the yellow catfish Elovl8 was highly conserved with other homologs in teleosts, sharing similar structural characteristics (including six conserved transmembrane α-helical domains, four conserved elongase motifs, and three highly conserved cysteine residues). Meanwhile, comparisons of genetic synteny confirmed that the elovl8 gene identified from the yellow catfish was the homolog of elovl8b in other teleosts, and thus, the elovl8a gene was lost in the genome of the yellow catfish. Gene structure analysis revealed that the elovl8b gene contained eight exons and seven introns, which was highly conserved in teleosts, implying the functional conservation among various fish species. Tissue distribution analysis detected by real-time quantitative PCR (RT-qPCR) showed that the elovl8 gene was extensively expressed in all detected tissues except eyes, with high expression levels in the intestine and liver. Temporal expression analysis revealed that the expression level of elovl8 was stably expressed in the early 12 h after fertilization, and then dramatically decreased at 24, 48, 72, and 96 h after fertilization, implying that elovl8 is required for HUFA biosynthesis in the early development stages. Functional experiments showed that the expression of the elovl8 gene was stimulated after feeding with egg yolk but was not obviously affected after feeding with halogenated worms, indicating that diets full of HUFAs can inhibit the expression of elovl8 in yellow catfish. Our findings will help us to better understand the evolutionary and functional characteristics of elovl8 in teleosts, and lay a solid basis for investigating the regulation mechanism of HUFA biosynthesis.

Natural phosphorus-ferromanganese ore-based composites for the simultaneous remediation of arsenic- and lead-co-contaminated groundwater: synergistic effectiveness, kinetics, and mechanisms - Hongli Lu; Xiangjian Xu; Yu Yang; Han Xiao; Fu Xia; Xu Han; Sheng Deng; Shuxuan Wu; Xingang Wang; Yonghai Jiang; Qinghua Yan (Environmental Science and Pollution Research, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

Telomere length, oxidative stress and their links with growth and survival in a lizard facing climate warming - Qiong Zhang; Xing-Zhi Han; Pablo Burraco; Xin Hao; Li-Wei Teng; Zhen-Sheng Liu; Fu-Shun Zhang; Wei-Guo Du (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Host trehalose metabolism disruption by validamycin A results in reduced fitness of parasitoid offspring - Yan Song; Fengming Gu; Yijiangcheng Li; Weihong Zhou; Fu-an Wu; Jun Wang; Sheng Sheng (Pesticide Biochemistry and Physiology, 2023)

Inhibiting or promoting: The industry heterogeneity of board interlocks and corporate social responsibility in China - Shiquan Wang; Sheng Gao; Yao Fu (Journal of Cleaner Production, 2023)

Biorthogonal wavelet energy entropy method with different time windows for strong interference processing of GPR signals - Liang Zhang; Sheng Zhang; Tonghua Ling; Fu Huang (Journal of Applied Geophysics, 2023)

A versatile organic silicate aluminum hybrid coagulant for broad-spectrum removal of heavy metal ions - Jin-Wei Liu; Tao Fu; Guang-Dong Sun; Xiao-Ran Shen; Sheng Liu; Yang He; Yi Xu; Hua-Zhang Zhao (Chemical Engineering Journal, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Transcription factor ELK1 regulates the expression of histone 3 lysine 9 to affect developmental potential of porcine preimplantation embryos - Yuanshen Zhao; Yanhui Zhai; Cong Fu; Lijing Shi; Xiangjie Kong; Qi Li; Hao Yu; Xinglan An; Sheng Zhang; Ziyi Li (Theriogenology, 2023)

Melatonin alleviates cisplatin-induced mice spermatogenesis defects - Zhu Peng; Wang Zhi Xin; Zhang Yu Sheng; Teng Zi; Liu Ya Nan; Wang Ze Lin; Liu Fu Jun; Liu Xue Xia (Reproductive Toxicology, 2023)

Construction ceramsite from low-silicon red mud: Design, preparation, and sintering mechanism analysis - Zhuo Liu; Rongxin Guo; Xiao-Yong Wang; Chaoshu Fu; Run-sheng Lin (Process Safety and Environmental Protection, 2023)

Identification and functional study of detoxification-related genes in response to tolfenpyrad stress in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Xin Pan; Jian-Hao Ding; Shuai-Qi Zhao; Hui-Cong Shi; Wang-Long Miao; Fu-An Wu; Sheng Sheng; Wei-Hong Zhou (Pesticide Biochemistry and Physiology, 2023)

Design, synthesis and biological activity of novel triketone herbicides containing natural product fragments - Zi-Bin Jiang; Shuang Gao; Wei Hu; Bo-Ren Sheng; Juan Shi; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

An improved time–depth dual porosity evolution model and a new parameter for tight sandstone reservoir quality evaluation - Zhen Zhao; Zhen Liu; Faqi He; Wei Zhang; Min Li; Yingjie Hou; Sheng Fu; Maolin Zhu (Journal of Asian Earth Sciences, 2023)

A yolk-shell Pd decorated Au@CeO2 with Schottky junction for long-lived charge separation and bandgap optimization to enhance sonodynamic therapy - Weiwei Sheng; Xiunan Wu; Mengying Fu; Cheng Chen; Zetai Bai; Mengyuan Xing; Chun Zhang; Lijuan Chong; Jingjing Li; Fenglei Gao (Chemical Engineering Journal, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Essential oil diversity of Cinnamomum parthenoxylon (Jack) Meisner from China - Fengying Qiu; Haikuan Yang; Chao Fu; Songsong Zhou; Yajing Sheng; Ting Zhang (South African Journal of Botany, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Efficient utilization of biogenic manganese oxides in bioaugmentation columns for remediation of thallium(I) contaminated groundwater - Liangjing Zhang; Yu Yang; Xiangjian Xu; Sheng Deng; Han Xiao; Xu Han; Fu Xia; Yonghai Jiang (Journal of Hazardous Materials, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Constructing functional thermal-insulation-layer on Co3O4 nanosphere for reinforced local-microenvironment photothermal PMS activation in pollutant degradation - Mengting Liu; Hongyang Zhu; Rongrong Du; Wuxiang Zhang; Weilong Shi; Zengjing Guo; Sheng Tang; Edison Huixiang Ang; Jun Yang; Jianming Pan; Fu Yang (Journal of Environmental Chemical Engineering, 2023)

Lanthanide bimetallic MOF-based fluorescent sensor for sensitive and visual detection of sulfamerazine and malachite - Xiaoyue Yue; Long Fu; Yan Li; Sheng Xu; Xin Lin; Yanhong Bai (Food Chemistry, 2023)

Engineered urinary-derived extracellular vesicles loaded nanoenzymes as Trojan horses to regulate the inflammatory microenvironment for treatment of Alzheimer's disease - Zetai Bai; Kezhen Ge; Jingjing Fu; Dehong Yu; Zhiyuan Hua; Senlin Xue; Zheng Li; Weiwei Sheng; Xiunan Wu; Fenfang Gao; Deqin Geng; Fenglei Gao (Chemical Engineering Journal, 2023)

Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Li Bai; Xiao-Lin Cai; Man-Yu Li; Fu-Xiao Wang; Chuan-Shan Zou; Jun-Sheng Zhang; Ming-Yu Xie; Feng-Hui Qi; Tian-Zhong Jing (Journal of Pest Science, 2023)

Causes of the discordance in the south-north distribution of the 2017 Jiuzhaigou earthquake sequences - Zhi-Tong Jin; Jia-Lu Liu; Yong-Ge Wan; Shu-Zhong Sheng; Fu-Chang Wang; Xiao-Tao Zhang; Gan Feng (Applied Geophysics, 2023)

Heavy metals in influent and effluent from 146 drinking water treatment plants across China: Occurrence, explanatory factors, probabilistic health risk, and removal efficiency - Kunfeng Zhang; Sheng Chang; Qi Zhang; Yunsong Bai; Enrui Wang; Moli Zhang; Qing Fu; Liangliang Wei; Yanling Yu (Journal of Hazardous Materials, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

One positive part of copper ion on biocatalysts: CNPs@Cu-Trypsin-assisted aqueous extraction technique for simultaneous exploration of edible insect oil and protein - Jin-Zheng Wang; Cheng-Kun Wu; Xin-Ying Wang; Yuan-Zhi Xu; Richard Ansah Herman; Sheng Sheng; Shuai You; Jun Wang; Fu-An Wu (Chemical Engineering Journal, 2023)

The SWADE model for landslide dating in time series of optical satellite imagery - Sheng Fu; Steven M. de Jong; Axel Deijns; Marten Geertsema; Tjalling de Haas (Landslides, 2023)
Landslides are destructive natural hazards that cause substantial loss of life and impact on natural and built environments. Landslide frequencies are important inputs for hazard assessments. However, dating landslides in remote areas is often challenging. We propose a novel landslide dating technique based on Segmented WAvelet-DEnoising and stepwise linear fitting (SWADE), using the Landsat archive (1985–2017). SWADE employs the principle that vegetation is often removed by landsliding in vegetated areas, causing a temporal decrease in normalized difference vegetation index (NDVI). The applicability of SWADE and two previously published methods for landslide dating, harmonic modelling and LandTrendr, are evaluated using 66 known landslides in the Buckinghorse River area, northeastern British Columbia, Canada. SWADE identifies sudden changes of NDVI values in the time series and this may result in one or more probable landslide occurrence dates. The most-probable date range identified by SWADE detects 52% of the landslides within a maximum error of 1 year, and 62% of the landslides within a maximum error of 2 years. Comparatively, these numbers increase to 68% and 80% when including the two most-probable landslide date ranges, respectively. Harmonic modelling detects 79% of the landslides with a maximum error of 1 year, and 82% of the landslides with a maximum error of 2 years, but requires expert judgement and a well-developed seasonal vegetation cycle in contrast to SWADE. LandTrendr, originally developed for mapping deforestation, only detects 42% of landslides within a maximum error of 2 years. SWADE provides a promising fully automatic method for landslide dating, which can contribute to constructing landslide frequency-magnitude distributions in remote areas.

An enhanced tilted-angle acoustic tweezer for mechanical phenotyping of cancer cells - Hanlin Wang; Joe Boardman; Xiaoyan Zhang; Chao Sun; Meng Cai; Jun Wei; Zhiqiang Dong; Mingqian Feng; Dongfang Liang; Sheng Hu; Yu Qian; Shuang Dong; et al. (Analytica Chimica Acta, 2023)

EchoAI: A deep-learning based model for classification of echinoderms in global oceans - Zhinuo Zhou; Ge-Yi Fu; Yi Fang; Ye Yuan; Hong-Bin Shen; Chun-Sheng Wang; Xue-Wei Xu; Peng Zhou; Xiaoyong Pan (Frontiers in Marine Science, 2023)
Introduction In response to the need for automated classification in global marine biological studies, deep learning is applied to image-based classification of marine echinoderms. Methods Images of marine echinoderms are collected and classified according to their systematic taxonomy. The images belong to 5 classes, 38 orders, 145 families, 459 genera, and 1021 species, respectively. The deep learning model, EfficientNetV2, outperforms the competing model and is chosen for developing the automated classification tool, EchoAI. Then, the EfficientNetV2-based tool, EchoAI is applied to each taxonomic level. Results The accuracy for the test dataset was 0.980 (class), 0.876 (order), 0.738 (family), 0.612 (genus), and 0.469 (species), respectively. Online prediction service is provided. Discussion The EchoAI model and results are facilitated for investigating the diversity, abundance and distribution of species at the global scale, and the methodological strategy can also be applied to image classification of other categories of marine organisms, which is of great significance for global marine studies. EchoAI is freely available at http://www.csbio.sjtu.edu.cn/bioinf/EchoAI/ for academic use.

Ellagic acid induces apoptosis and autophagy in colon cancer through the AMPK/mTOR pathway - Xiong Ni; Fu-Sheng Shang; Ting-Feng Wang; De-Jun Wu; Da-Gui Chen; Biao Zhuang (Tissue and Cell, 2023)

PFO5DoDA disrupts hepatic homeostasis primarily through glucocorticoid signaling inhibition - Chang Wang; Huayu Fu; Jun Yang; Lei Liu; Fenghong Zhang; Chunyu Yang; Hongyuan Li; Jiamiao Chen; Qi Li; Xiaolin Wang; Yaorui Ye; Nan Sheng; et al. (Journal of Hazardous Materials, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Particulate nitrated aromatic compounds from corn straw burning: Compositions, optical properties and potential health risks - Runqi Zhang; Wei Song; Yanli Zhang; Xinming Wang; Xuewei Fu; Sheng Li (Environmental Pollution, 2023)

Aqueous strategy for controllable in-situ growth of high-quality perovskite nanocrystals@polymer films toward white light-emitting diodes - Hao Zhang; Sheng Cao; Jialiang Jiang; Qian Sun; Jizhong Liu; Deliu Ou; Jialong Zhao; Weiyou Yang; Hui Fu; Jinju Zheng (Chemical Engineering Journal, 2023)

Spinal MCP-1 Contributes to Central Post-stroke Pain by Inducing Central Sensitization in Rats - Fei Yang; Jun-Jie Jing; Si-Yin Fu; Xiu-Zhu Su; Yu-Ling Zhong; Dong-Sheng Chen; Xiao-Zhi Wu; Yi-Qing Zou (Molecular Neurobiology, 2023)

Assessing accuracy of genomic breeding values of selection candidates under biosecurity restrictions by progeny testing in Chinese shrimp Fenneropenaeus chinensis - Mianyu Liu; Ping Dai; Jie Kong; Xianhong Meng; Juan Sui; Kun Luo; Baolong Chen; Qiang Fu; Baoxiang Cao; Jiawang Cao; Sheng Luan (Aquaculture, 2023)

A linkage between early Silurian Nb-REE enriched alkaline magmatism and Neoproterozoic subduction metasomatized mantle in South Qinling, Central China - Jian-Hui Su; Xin-Fu Zhao; Xiao-Chun Li; Sheng-Ren Chang; Yuan-Bao Wu; Carl Spandler (Lithos, 2023)

Deciphering roles of microbiota in arsenic biotransformation from the earthworm gut and skin - Hong-Tao Wang; Zong-Zheng Liang; Jing Ding; Gang Li; Sheng-Lei Fu; Dong Zhu (Journal of Hazardous Materials, 2023)

A novel thermosensitive persulfate controlled-release hydrogel based on agarose/silica composite for sustained nitrobenzene degradation from groundwater - Shuxuan Wu; Sheng Deng; Fu Xia; Xu Han; Tianyu Ju; Han Xiao; Xiangjian Xu; Yu Yang; Yonghai Jiang; Beidou Xi (Journal of Hazardous Materials, 2023)

A bacterial cellulose-based separator with tunable pore size for lithium-ion batteries - Chen Cheng; Rendang Yang; Yang Wang; Danning Fu; Jie Sheng; Xiaohui Guo (Carbohydrate Polymers, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Periostin regulation and cartilage degradation early after anterior cruciate ligament reconstruction - Cale A. Jacobs; Laura E. Keller; Sheng Zhang; Qin Fu; Emily R. Hunt; Austin V. Stone; Caitlin E. W. Conley; Christian Lattermann; Lisa A. Fortier (Inflammation Research, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Post-failure analysis of landslide blocking river using the two-phase double-point material point method: a case of western Hubei, China - Wenjie Du; Qian Sheng; Xiaodong Fu; Jian Chen; Pengfei Wei; Yongqiang Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Stability evaluation of the high fill deposit slope subjected to rainfall considering water deterioration - Zhenping Zhang; Qian Sheng; Dingfeng Song; Xiaodong Fu; Yongqiang Zhou; Juehao Huang (Bulletin of Engineering Geology and the Environment, 2023)

Potassium isotope fractionation during granitic magmatic differentiation: Mineral-pair perspectives - Tian-Yi Huang; Fang-Zhen Teng; Ze-Zhou Wang; Yong-Sheng He; Zhi-Chao Liu; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2023)

Adsorptive removal of anionic azo dye by Al3+-modified magnetic biochar obtained from low pyrolysis temperatures of chitosan - Ru Jiang; Hua-Yue Zhu; Yong-Qian Fu; Xin Li; Sheng-Tao Jiang; Jian-Bing Li (Environmental Science and Pollution Research, 2023)

Performance of oxalate-doped hydroxyapatite as well as relative contribution of oxalate and phosphate for aqueous lead removal - Haojie Fu; Xinxin Li; Guoqing Dai; Maojuan Bai; Wei Sheng; Xu Zhang; Juan Liu; Lei Wang (Science of The Total Environment, 2023)

Joint passive seismic imaging based on surface wave inversion and reflection wavefield retrieval: A case study in the sedimentary basin areas adjacent to Well Songke-2 - Zhong-Yuan Jin; He-Sheng Hou; Wei Fu; Pan Zhang; Dong-Zhao An; Yong Hu (Journal of Applied Geophysics, 2023)

Improving tea (Camellia sinensis) quality, economic income, and environmental benefits by optimizing agronomic nitrogen efficiency: A synergistic strategy - Sheng Tang; Haoran Fu; Wankun Pan; Jingjie Zhou; Meng Xu; Kefeng Han; Kaijun Chen; Qingxu Ma; Lianghuan Wu (European Journal of Agronomy, 2023)

Can phosphobacteria simultaneously achieve phosphorus recovery and Pb2+ removal from wastewater by biomineralization? - Pei Zhang; Yi-Min Ding; Tian-Lei Zhao; Yu-Han Wang; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Chemical Engineering Journal, 2023)

Efficient inverted CsPbI3 perovskite solar cells fabricated in common air - Chunyan Lu; Xiaodong Li; Xuemin Guo; Sheng Fu; Wenxiao Zhang; Haobo Yuan; Junfeng Fang (Chemical Engineering Journal, 2023)

Light-enhanced transparent hydrogel for uric acid and glucose detection by four different analytical platforms - Wei Mao; Xingwei Cai; Ruirong Pan; Sheng Tang; Fu Yang; Yanjuan Cui; Jun Sun; Wei Shen (Analytica Chimica Acta, 2023)

Supramolecular self-assembled AIE molecules are used in the search for target proteins in norcantharidin - Lijuan Ma; Xuetong Sun; Wenwen Ji; Bei Zhang; Jianting Li; Wenjuan Fu; Xiangying Zhang; Wenhui Qian; Enze Sheng; Dong Zhu (Analytica Chimica Acta, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

miR-182-5p Delivered by Plasma Exosomes Promotes Sevoflurane-Induced Neuroinflammation and Cognitive Dysfunction in Aged Rats with Postoperative Cognitive Dysfunction by Targeting Brain-Derived Neurotrophic Factor and Activating NF-κB Pathway - Fu-sheng Wei; Mu-wen Rao; Yuan-lu Huang; Shi-biao Chen; Yu-qian Wu; Lei Yang (Neurotoxicity Research, 2022)

Local application of triamcinolone acetonide-conjugated chitosan membrane to prevent benign biliary stricture - Tao Wang; Shibo Zhang; Lianmin Wang; Kun Su; Zhiyi Tang; Haiyu He; Yanmei Shi; Yaqiong Liu; Mengyao Zheng; Wen Fu; Sheng Hu; Xiaowen Zhang; et al. (Drug Delivery and Translational Research, 2022)

Acute transcriptomic changes in murine RAW 264.7 cells following pseudorabies virus infection - Chao Tong; Peng-Fei Fu; Sheng-Li Ming; Lei Zeng; He-Shui Zhu; Jiang Wang (Archives of Virology, 2022)

Research on Structural Failure Analysis and Strengthening Design of Offshore Wind Turbine Blades - Xiaohan Fu; Meiping Sheng (Journal of Marine Science and Engineering, 2022)
The existing blade protection mechanisms are highly dependent on the control system and its power supply. Safety of offshore wind turbines cannot be guaranteed under extreme weather when the control protection mechanisms fail. So far, not enough consideration has been given to the above problems in mechanical design for protecting wind turbine blades. In this paper, a reinforcing cable component (RCC) is proposed to improve the resistance ability of offshore wind turbine blades. The static model of the blades with reinforcing cable component was presented. The Finite Element (FE) simulation was performed for a 5 MW offshore wind turbine and load reduction effect of connection location for RCC was discussed according to the FE results. A static strain verification test was carried out. Simulation and test results indicate that the proposed reinforcing cable component effectively reduces the strain as well as the tip displacement of the blades. The proposed mechanical structure will help to enhance the survival ability of offshore wind turbine blades when the control protection system fails.

The association between hearing threshold and urinary personal care and consumer product metabolites in middle-aged and elderly people from the USA - Yan-Peng Fu; Wen-Yu Chen; Li-Qing Guo; Ya-Qiong Zhu; Jia-Sheng Yuan; Yue-Hui Liu (Environmental Science and Pollution Research, 2022)

Epigallocatechin-3-Gallate Pretreatment Improves Autologous Adipose-derived Stem Cells Against Rheumatoid Arthritis-induced Neuroinflammation in the Brain of Collagen-induced Rats - Ming-Shan Chen; Bruce Chi-Kang Tsai; Maria Angelina Sitorus; Chia-Hua Kuo; Wei-Wen Kuo; Tung-Sheng Chen; Chien-Yao Fu; Tsung-Jung Ho; Chih-Yang Huang; Da-Tong Ju (Neurotoxicity Research, 2022)

Investigation of migration rule of rainwater for sponge city roads under different rainfall intensities - Zhe Qin; Yujing Yao; Jingwei Zhao; Houli Fu; Sheng Zhang; Liyuan Qiu (Environmental Geochemistry and Health, 2022)

Evolution stage, spatial and temporal variabilities of granite landforms in the Mount Wugongshan in Jiangxi Province of South China - Le Chai; Cun-di Zhong; Fu-sheng Guo; Xin-shu Huang; Dao-ying Wang; Chong-jian Shao; Liu-qin Chen (Journal of Mountain Science, 2022)

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Cavitation–Silt Erosion Behavior and Failure Mechanism of an HVOF-Sprayed WC-Cr3C2-Ni Coating for Offshore Hydraulic Machinery - Jinran Lin; Sheng Hong; Yuan Zheng; Wei Sun; Zhengwei Zhang; Min Kang; Xiuqing Fu (Journal of Marine Science and Engineering, 2022)
WC-Cr3C2-Ni coatings are a vital class of hard ceramic/cermet coatings with potential applications as wear-resistant materials. However, their erosion wear behavior in 3.5 wt.% sodium chloride medium (SCM) remains largely unexplored. The present study investigated the cavitation–silt erosion (CSE) behavior in 3.5 wt.% SCM of WC-Cr3C2-Ni coatings sprayed with high-velocity oxygen–fuel (HVOF) under different flow velocities (FVs) and sand concentrations (SCs). Comparing the WC-Cr3C2-Ni coating with the 1Cr18Ni9Ti stainless steel, the first possessed superior CSE resistance in 3.5 wt.% SCM in a full range of FV and SC. Meanwhile, the coating appeared more influenced by FV and less influenced by SC, which was indicated by the fact that the amplification of VLR value (377.1%) when the FV ranged from 23.4 to 41.9 m·s−1 was larger than that (129.8%) when the SC increased from 10 kg·m−3 to 35 kg·m−3. With increasing FV and SC, the CSE process of the WC-Cr3C2-Ni coating in 3.5 wt.% SCM mainly included the discontinuous corrosion product films, erosion pits, fracturing of hard-phase grains, and micro-cutting of soft binder matrix, as well as crater formation and coating spalling.

A Frequency-Dependent Assimilation Algorithm: Ensemble Optimal Smoothing - Zhongjie He; Yueqi Zhao; Xiachuan Fu; Xin Sheng; Siwen Xu (Journal of Marine Science and Engineering, 2022)
Motivated by the need for a simple and effective assimilation scheme that could be used in a relocatable ocean model, a new assimilation algorithm called ensemble optimal smoothing (EnOS) was developed. This scheme was a straightforward extension of the ensemble optimal interpolation (EnOI) by involving time correlation information in the Kalman gain. The main advantage of this scheme was the ability to estimate the present state from the time history of observation. We first examined the new scheme in an ideal ocean model using simulated observations. Further applying these two assimilation schemes to the Chinese offshore and adjacent waters, the root-mean-square error (RMSE) of the EnOS scheme was reduced by 6.4% relative to EnOI. The results showed that the EnOS was more efficient and effective in eliminating model errors when compared to the EnOI scheme.

The Dynamic Deformation Properties of Rock Materials Under Different Types of Seismic Load - Yongqiang Zhou; Qian Sheng; Xiaodong Fu; Haifeng Ding (Rock Mechanics and Rock Engineering, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Novel SNPs in the 3′UTR Region of GHRb Gene Associated with Growth Traits in Striped Catfish (Pangasianodon hypophthalmus), a Valuable Aquaculture Species - Liang-Sen Jiang; Zhuo-Hao Ruan; Zhi-Qiang Lu; Yi-Fu Li; Yuan-Yuan Luo; Xi-Quan Zhang; Wen-Sheng Liu (Fishes, 2022)
The striped catfish, Pangasianodon hypophthalmus is an important freshwater aquaculture species in Southeast Asian countries due to its rapid growth. The growth hormone receptor (GHR) is a significant regulatory factor for the growth axis and has great potential applications in animal genetic breeding. This study aims to characterize the GHRb cDNA of the striped catfish and analyze the distribution of its mRNA. Screening of single nucleotide polymorphisms’ (SNPs) loci and diplotypes was performed to provide basic information for the assisted selection of molecular markers in genetic breeding. The results showed that the GHRb cDNA of striped catfish had 2791 bp, which encoded for 569 amino acids. In a phylogenyic study, the ghrb of the striped catfish was clustered with those of other catfish and they were highly homologous. Quantitative real-time PCR (qRT-PCR) experiments showed that GHRb mRNA was expressed in ten different organs of the striped catfish, with the highest expression level in the liver. Five SNP and a haplotype block were identified in the 3′UTR of the GHRb gene using the direct sequencing of 307 individuals. Three haplotypes were found and four diplotypes were constructed. The association analysis revealed that these polymorphisms were significantly associated with growth traits in the striped catfish (p

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Role of host plants in the suitability and dispersal of an omnivorous predator Arma chinensis Fallou (Hemiptera: Pentatomidae: Asopinae) in a biological control context - Ming-Zhen Pan; Zhi-Xiao Fu; Yu-Yan Li; Hong-Yin Chen; Li-Sheng Zhang; Tong-Xian Liu (Journal of Plant Diseases and Protection, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Spatiotemporal variation in nitrogen and phosphorus levels and microbial community in the upstream water transport channel to the Douhe Reservoir - Yueting Fan; Qing Fu; Shusong Zhang; Moli Zhang; Sheng Chang; Shaoyan Zhao; Minling Wang (Environmental Science and Pollution Research, 2022)

Optimizing Hard Clam Production in Taiwan by Accounting for Nonlinear Effects of Stocking Density and Feed Costs on Farm Output of Clams - Jie-Min Lee; Sheng-Hung Chen; Yi-Chung Lee; Jung-Fu Huang; Christian Schafferer; Chun-Yuan Yeh; Ti-Wan Kung (Fishes, 2022)
Despite mass mortality, hard clams remain among the main cultured shellfish in Taiwan. Using cross-sectional data, this study applies threshold regression modeling with stocking density and feed costs as the threshold variables to explore the nonlinear relationship between input and output factors. The findings show that the production output levels may be increased by different combinations of factor inputs and variations in input factors. More specifically, the higher output levels may be achieved by increasing labor input while reducing capital input factors in farming households with a higher stocking density (HSD > 1,087,870 inds/ha) or higher feed cost (HFC > 13,889 NTD/ha). Farming households with a lower stocking density (LSD ≤ 1,087,870 inds/ha) may enhance production output levels by increasing feed input while reducing capital inputs. Moreover, the maximum output level of HSD and HFC farming households was estimated to reach 9255 kg/ha and 9807 kg/ha, respectively. Results of the production output simulation suggest that the feeding cost per hectare in LSD households should not exceed 25,119 NTD to avoid overfeeding, which may cause culture deterioration and lower survival rates. As such, farmers are advised to adjust their feed costs according to the stocking density to maximize production output.

An ortholog of the MADS-box gene SEPALLATA3 regulates stamen development in the woody plant Jatropha curcas - Mei-Li Zhao; Zhi-Fang Zhou; Mao-Sheng Chen; Chuan-Jia Xu; Zeng-Fu Xu (Planta, 2022)

Impact of N application rate on tea (Camellia sinensis) growth and soil bacterial and fungi communities - Sheng Tang; Jingjie Zhou; Wankun Pan; Rui Tang; Qingxu Ma; Meng Xu; Tong Qi; Zhengbo Ma; Haoran Fu; Lianghuan Wu (Plant and Soil, 2022)

Soil types determine vegetation communities along a toposequence in a dolomite peak-cluster depression catchment - Qingmei Meng; Sheng Wang; Zhiyong Fu; Yusong Deng; Hongsong Chen (Plant and Soil, 2022)

Risk assessment and support design optimization of a high slope in an open pit mine using the jointed finite element method and discontinuous deformation analysis - Jingyu Kang; Daochun Wan; Qian Sheng; Xiaodong Fu; Xin Pang; Luqing Xia; De Li (Bulletin of Engineering Geology and the Environment, 2022)

Haze management: is urban public transportation priority effective? - Ziyu Zhai; Xiaoling Fu; Ming Yi; Mingyue Sheng; Fengtao Guang (Environmental Science and Pollution Research, 2022)

A new picrotoxane-type sesquiterpene from Dendrobium nobile Lindl - Pei Wang; Xin Chen; Cai-Hong Cai; Fan-Dong Kong; Sheng-Zhuo Huang; Jing-Zhe Yuan; Xing-Lian Xu; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2022)

The Dynamic Mechanical Properties of a Hard Rock Under True Triaxial Damage-Controlled Dynamic Cyclic Loading with Different Loading Rates: A Case Study - Yongqiang Zhou; Qian Sheng; Nana Li; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

The failure mode of transmission tower foundation on the landslide under heavy rainfall: a case study on a 500-kV transmission tower foundation on the Yanzi landslide in Badong, China - Yongqiang Zhou; Qian Sheng; Jian Chen; Nana Li; Xiaodong Fu; Yingbo Zhou (Bulletin of Engineering Geology and the Environment, 2022)

A Neural Circuit Mechanism Controlling Breathing by Leptin in the Nucleus Tractus Solitarii - Hongxiao Yu; Luo Shi; Jinting Chen; Shirui Jun; Yinchao Hao; Shuang Wang; Congrui Fu; Xiang Zhang; Haiyan Lu; Sheng Wang; Fang Yuan (Neuroscience Bulletin, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Influences of water on the microstructure and mechanical behavior of the Xigeda formation - Xiaodong Fu; Yuxiang Du; Qian Sheng; Zhenping Zhang; Juehao Huang (Bulletin of Engineering Geology and the Environment, 2022)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

A novel BRET based genetic coded biosensor for apoptosis detection at deep tissue level in live animal - Yueling Zhang; Juan Hu; Meijuan Yu; Zhirong Wang; Hucheng Qing; Huheng Fu; Liudi Yuan; Fei Li; Sheng Zhao (Apoptosis, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

Pericyte hypoxia-inducible factor-1 (HIF-1) drives blood-brain barrier disruption and impacts acute ischemic stroke outcome - Chih-Chieh Tsao; Julia Baumann; Sheng-Fu Huang; Diana Kindler; Aileen Schroeter; Nicole Kachappilly; Max Gassmann; Markus Rudin; Omolara O. Ogunshola (Angiogenesis, 2021)
Pericytes play essential roles in blood-brain barrier integrity and their dysfunction is implicated in neurological disorders such as stroke although the underlying mechanisms remain unknown. Hypoxia-inducible factor-1 (HIF-1), a master regulator of injury responses, has divergent roles in different cells especially during stress scenarios. On one hand HIF-1 is neuroprotective but on the other it induces vascular permeability. Since pericytes are critical for barrier stability, we asked if pericyte HIF-1 signaling impacts barrier integrity and injury severity in a mouse model of ischemic stroke. We show that pericyte HIF-1 loss of function (LoF) diminishes ischemic damage and barrier permeability at 3 days reperfusion. HIF-1 deficiency preserved barrier integrity by reducing pericyte death thereby maintaining vessel coverage and junctional protein organization, and suppressing vascular remodeling. Importantly, considerable improvements in sensorimotor function were observed in HIF-1 LoF mice indicating that better vascular functionality post stroke improves outcome. Thus, boosting vascular integrity by inhibiting pericytic HIF-1 activation and/or increasing pericyte survival may be a lucrative option to accelerate recovery after severe brain injury.

New types of ATP ‐grasp ligase are associated with the novel pathway for complicated mycosporine‐like amino acid production in desiccation‐tolerant cyanobacteria - Zhong‐Chun Zhang; Kai Wang; Fu‐Hua Hao; Jin‐Long Shang; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Mycosporine‐like amino acids (MAAs) were widespread in diverse organisms to attenuate UV radiation. We recently characterized the large, complicated MAA mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) in desert cyanobacterium Nostoc flagelliforme . Synthesis of this MAA requires the five‐gene cluster mysABDC2C3 . Here, bioinformatic analysis indicated that mysC duplication within five‐gene mys clusters is strictly limited to drought‐tolerant cyanobacteria. Phylogenic analysis distinguished these duplicated MysCs into two clades that separated from canonical MysCs. Heterologous expression of N. flagelliforme mys genes in Escherichia coli showed that MysAB produces 4‐deoxygadusol. The ATP‐grasp ligase of MysC3 catalyses the linkage of the δ‐ or ε‐amino group of ornithine/lysine to 4‐deoxygadusol, yielding mycosporine‐ornithine or mycosporine‐lysine respectively. The ATP‐grasp ligase of MysC2 strictly condenses the α‐amino group of mycosporine‐ornithine to another 4‐deoxygadusol. MysD (D‐Ala–D‐Ala ligase) functions following MysC2 to catalyse the formation of mycosporine‐2‐(4‐deoxygadusolyl‐ornithine). High arginine content likely provides a greater pool of ornithine over other amino acids during rehydration of desiccated N. flagelliforme . Duplication of ATP‐grasp ligases is specific for the use of substrates that have two amino groups (such as ornithine) for the production of complicated MAAs with multiple chromophores. This five‐enzyme biosynthesis pathway for complicated MAAs is a novel adaptation of cyanobacteria for UV tolerance in drought environments.

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

A review of the botany, traditional uses, phytochemistry and pharmacology of Nepeta tenuifolia Briq. - Mingqiu Shan; Yulan Jiang; Yuanyuan Fu; Yongyi Zhou; Zhihui Lu; Sheng Yu; Hui Yan; Chanchan Liu; Peidong Chen; Beihua Bao; Li Zhang; Qinan Wu (Phytochemistry Reviews, 2021)

Home-Use and Real-Time Sleep-Staging System Based on Eye Masks and Mobile Devices with a Deep Learning Model - Tsung-Hao Hsieh; Meng-Hsuan Liu; Chin-En Kuo; Yung-Hung Wang; Sheng-Fu Liang (Journal of Medical and Biological Engineering, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Suppression of multiple reflection–refraction waves in the shallow low-velocity zone via vertical source combination - Suoliang Chang; Zhen Qu; Sheng Zhang; Yanning Fu; Qiang Chen (Acta Geophysica, 2021)

A Numerical Meso-Scale Elasto-Plastic Damage Model for Modeling the Deformation and Fracturing of Sandstone Under Cyclic Loading - Tao Xu; Meng Fu; Sheng-qi Yang; Michael J. Heap; Guang-lei Zhou (Rock Mechanics and Rock Engineering, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

A Survey on How Ocular Surface Demodex Infestation Interactively Associates with Diabetes Mellitus and Dry Eye Disease - Chang Huang; Shuze Chen; Sheng Fu; Yingli Li; Zhenhao Li; Siqi Li; Xiaoqian Liang; Zihong Wang; Zhoucheng Wang; Yifan Chen; Qixin Deng; Guoguo Yi; et al. (Acta Parasitologica, 2021)
Purpose Prevention of ocular surface (OS) Demodex infestation plays an important role in OS hygiene and variety of factors may be associated with it, in which diabetes mellitus (DM) or dry eye disease (DED) has caught the attention of most scholars. However, there has been no research on whether there was a potential interaction between DM and DED in the process of OS Demodex infestation. This cross-sectional study was implemented in Zhujiang Hospital of Southern Medical University. Methods Ophthalmologic interviews, questionnaires, and examinations were conducted. Factors including general information, DM status, dry eye condition, etc. were collected to study the correlation of DM and DED on OS Demodex infestation. Results After statistical analysis, we found that both DM ( P P = 0.013 R = 0.197, P R = 0.299, P P Conclusion This study provides a new evidence-based basis for clinical prevention and management of OS Demodex infestation.

High resolution mapping of nighttime light and air pollutants during the COVID-19 lockdown in Wuhan - Sheng Zheng; Yuyuan Fu; Yu Sun; Chengjie Zhang; Yueshe Wang; Eric Lichtfouse (Environmental Chemistry Letters, 2021)

Deformation of the Zhangjiazhuang high-speed railway tunnel: an analysis of causal mechanisms using geomorphological surveys and D-InSAR monitoring - Xing-min Meng; Tian-jun Qi; Yan Zhao; Tom Dijkstra; Wei Shi; Yin-fei Luo; Yuan-zhao Wu; Xiao-jun Su; Fu-meng Zhao; Jin-hui Ma; Yi Zhang; Guan Chen; et al. (Journal of Mountain Science, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Litter addition and understory removal influenced soil organic carbon quality and mineral nitrogen supply in a subtropical plantation forest - Xiang-Min Fang; G. Geoff Wang; Zhi-Jun Xu; Ying-Ying Zong; Xiu-Lan Zhang; Jian-Jun Li; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Lactobacillus rhamnosus JYLR-005 Prevents Thiram-Induced Tibial Dyschondroplasia by Enhancing Bone-Related Growth Performance in Chickens - Fang Liu; Anan Kong; Pengfei Fu; Qin-qin Cao; Kun-sheng Tao; Di-yi Liu; Xue-bing Wang; Zong-xi Tong; Mujeeb Ur Rehman; Shu-cheng Huang (Probiotics and Antimicrobial Proteins, 2021)

Respiratory Control by Phox2b-expressing Neurons in a Locus Coeruleus–preBötzinger Complex Circuit - Na Liu; Congrui Fu; Hongxiao Yu; Yakun Wang; Luo Shi; Yinchao Hao; Fang Yuan; Xiangjian Zhang; Sheng Wang (Neuroscience Bulletin, 2021)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

Analysis of landslide stability under seismic action and subsequent rainfall: a case study on the Ganjiazhai giant landslide along the Zhaotong-Qiaojia road during the 2014 Ludian earthquake, Yunnan, China - Xiaodong Fu; Qian Sheng; Guo Li; Zhenping Zhang; Yongqiang Zhou; Yuxiang Du (Bulletin of Engineering Geology and the Environment, 2020)

Comparative transcriptome analysis of gynoecious and monoecious inflorescences reveals regulators involved in male flower development in the woody perennial plant Jatropha curcas - Mei-Li Zhao; Mao-Sheng Chen; Jun Ni; Chuan-Jia Xu; Qing Yang; Zeng-Fu Xu (Plant Reproduction, 2020)

Sauchinone: a prospective therapeutic agent-mediated EIF4EBP1 down-regulation suppresses proliferation, invasion and migration of lung adenocarcinoma cells - Sheng-Qian Li; Jing Feng; Ming Yang; Xiao-Peng Ai; Mei He; Fu Liu (Journal of Natural Medicines, 2020)

The Influence of Strain Rate on the Energy Characteristics and Damage Evolution of Rock Materials Under Dynamic Uniaxial Compression - Yongqiang Zhou; Qian Sheng; Nana Li; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Variations in vegetation dynamics and its cause in national key ecological function zones in China - Jiaqiang Du; Shifeng Fang; Zhilu Sheng; Jinhua Wu; Zhanjun Quan; Qing Fu (Environmental Science and Pollution Research, 2020)

Evaluation of dynamic stability and analysis of reinforcement measures of a landslide under seismic action: a case study on the Yanyangcun landslide - Xiaodong Fu; Qian Sheng; Wenjie Du; Hongru Mei; He Chen; Yuxiang Du (Bulletin of Engineering Geology and the Environment, 2020)

Transferability of a Conceptual Hydrological Model across Different Temporal Scales and Basin Sizes - Sheng Sheng; Hua Chen; Fu-Qiang Guo; Jie Chen; Chong-Yu Xu; Sheng-lian Guo (Water Resources Management, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Titanium dioxide nanoparticles induced the apoptosis of RAW264.7 macrophages through miR-29b-3p/NFAT5 pathway - Siyi Xu; Jing Sui; Yanyun Fu; Wenjuan Wu; Tong Liu; Sheng Yang; Geyu Liang (Environmental Science and Pollution Research, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

An approach to predicting the shear strength of soil-rock mixture based on rock block proportion - Zhenping Zhang; Qian Sheng; Xiaodong Fu; Yongqiang Zhou; Juehao Huang; Yuxiang Du (Bulletin of Engineering Geology and the Environment, 2020)

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Immunometabolism: new insights and lessons from antigen-directed cellular immune responses - Renata Ramalho; Martin Rao; Chao Zhang; Chiara Agrati; Giuseppe Ippolito; Fu-Sheng Wang; Alimuddin Zumla; Markus Maeurer (Seminars in Immunopathology, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Bisexual Fertile Triploid Zebrafish (Danio rerio): a Rare Case - Liangyue Peng; Wen Fu; Xianlong Wu; Sheng He; Han Zhao; Jinhui Liu; Wenbin Liu; Yamei Xiao (Marine Biotechnology, 2020)

Identification and characterization of two morphologically distinct stem cell subpopulations from human urine samples - An-Jing Chen; Jin-Kui Pi; Jun-Gen Hu; Yi-Zhou Huang; Hong-Wei Gao; Sheng-Fu Li; Jesse Li-Ling; Hui-Qi Xie (Science China Life Sciences, 2020)

Exogenous salicylic acid alleviates halosulfuron-methyl toxicity by coordinating the antioxidant system and improving photosynthesis in soybean (Glycine max Merr.) - Yuan-Fu Li; Lu-Lu Huang; Xiao-Liang Liu; Xue-Sheng Li; Hui-Hua Tan (Acta Physiologiae Plantarum, 2020)

Toonapolyynes A–D, new polyynes from Toona ciliata - Rong Wang; Fu-Qiang Ni; Jun Sang; Yao Zhang; Jia-Luo Huang; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Risk Assessment of Crop Production Amid Climate Change Based on the Principle of Maximum Entropy: A Case Study of Winter Wheat Production on the North China Plain - Zhan-biao Wang; Cheng-sheng Meng; Jing Chen; Fu Chen (International Journal of Plant Production, 2019)

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

Panax notoginsenoside Rb1 Restores the Neurotrophic Imbalance Following Photothrombotic Stroke in Rats - Chun-Yan Yang; Jian-Yu Yang; Yun-Xia Xiong; Xue-Feng Zhuang; Hui Su; Sheng Hu; Jia-Qing Ma; Xin-Fu Zhou; Hai-Yun Luo; Jun Sun (Neurotoxicity Research, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

miR-183-5p enhances the radioresistance of colorectal cancer by directly targeting ATG5 - Sheng Zheng; Yong-Fu Zhong; De-Ming Tan; Yue Xu; Huai-Xiang Chen; Dan Wang (Journal of Biosciences, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Tetramethylpyrazine ameliorates depression by inhibiting TLR4-NLRP3 inflammasome signal pathway in mice - Songnian Fu; Jiangtao Wang; Chenguang Hao; Haihong Dang; Sheng Jiang (Psychopharmacology, 2019)

Glacier extent changes and possible causes in the Hala Lake Basin of Qinghai-Tibet Plateau - Dong-Sheng Li; Bu-Li Cui; Ying Wang; Bei Xiao; Bao-Fu Jiang (Journal of Mountain Science, 2019)

Discrimination and evaluation Gentiana rigescens–Camellia sinensis with different planting year using Fourier transform infrared spectroscopy - Li-Ju Mi; Ji Zhang; Yan-Li Zhao; Zhi-Tian Zuo; Yuan-Zhong Wang; Fu-Sheng Li (Agroforestry Systems, 2019)

Two new noroleanane-type triterpenoid saponins from the stems of Stauntonia chinensis - Tong-Tong Feng; Hui-Zheng Fu; Yi-Sheng Yang; Zhi-Qiang Zhou; Mian Dai; Hong-Yu Bi; Dong Wang (Natural Product Research, 2019)

Nitrogen deposition effect on forest litter decomposition is interactively regulated by endogenous litter quality and exogenous resource supply - Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Song-Ze Wan; Yang Zhang; Chao Liang (Plant and Soil, 2019)

Regulation of flowering time via miR172-mediated APETALA2-like expression in ornamental gloxinia (Sinningia speciosa) - Xiao-yan Li; Fu Guo; Sheng-yun Ma; Mu-yuan Zhu; Wei-huai Pan; Hong-wu Bian (Journal of Zhejiang University-SCIENCE B, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Centrifugal model tests and numerical simulations for barrier dam break due to overtopping - Tian-long Zhao; Sheng-shui Chen; Chang-jing Fu; Qi-ming Zhong (Journal of Mountain Science, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Cerebrospinal fluid otorrhea secondary to congenital inner ear dysplasia: diagnosis and management of 18 cases - Bing Wang; Wen-jia Dai; Xiao-ting Cheng; Wen-yi Liuyang; Ya-sheng Yuan; Chun-fu Dai; Yi-lai Shu; Bing Chen (Journal of Zhejiang University-SCIENCE B, 2019)

The effects of simulated acid rain on internal nutrient cycling and the ratios of Mg, Al, Ca, N, and P in tea plants of a subtropical plantation - Xiao-Fei Hu; An-Qi Wu; Fang-Chao Wang; Fu-Sheng Chen (Environmental Monitoring and Assessment, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Total and available metal concentrations in soils from six long-term fertilization sites across China - Dong-Xing Guan; Fu-Sheng Sun; Guang-Hui Yu; Matthew L. Polizzotto; Yun-Gen Liu (Environmental Science and Pollution Research, 2018)

Origin of beaded tafoni in cliffs of Danxia landscapes, Longhushan Global Geopark, South China - Fu-sheng Guo; Liu-qin Chen; Huan Xu; Xin Liu (Journal of Mountain Science, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Polychlorinated biphenyls and their hydroxylated metabolites in the serum of e-waste dismantling workers from eastern China - Shengtao Ma; Guofa Ren; Xiangying Zeng; Zhiqiang Yu; Guoying Sheng; Jiamo Fu (Environmental Geochemistry and Health, 2018)

Gibberellin Inhibits Floral Initiation in the Perennial Woody Plant Jatropha curcas - Jialong Li; Bang-Zhen Pan; Longjian Niu; Mao-Sheng Chen; Mingyong Tang; Zeng-Fu Xu (Journal of Plant Growth Regulation, 2018)

Design of multi-layer coupling support and span of setup entry roof at depth - Hou-sheng Jia; Lu-yao Wang; Shao-wei Liu; Zhi-yao Feng; Meng-xiong Fu (Arabian Journal of Geosciences, 2018)

An inversion of transient electromagnetic data from a conical source - Hai-Yan Yang; Feng-Ping Li; Shen-En Chen; Jian-Hua Yue; Fu-Sheng Guo; Xiao Chen; Hua Zhang (Applied Geophysics, 2018)

Active earth pressure on translating rigid retaining structures considering soil arching effect - Yi-tao Zhou; Qing-sheng Chen; Fu-quan Chen; Xiao-hui Xue; Sudip Basack (European Journal of Environmental and Civil Engineering, 2018)

Experimental Investigation of the Influence of Drilling Arrangements on the Mechanical Behavior of Rock Models - Bin Huang; Wei-yao Guo; Zhi-yong Fu; Tong-bin Zhao; Lian-sheng Zhang (Geotechnical and Geological Engineering, 2018)

Plasma miR-124 Is a Promising Candidate Biomarker for Human Intracerebral Hemorrhage Stroke - Zifeng Wang; Gang Lu; Johnny Sze; Yao Liu; Sheng Lin; Hong Yao; Ji Zhang; Dan Xie; Quentin Liu; Hsiang-fu Kung; Marie Chia-mi Lin; Wai Sang Poon (Molecular Neurobiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Three-dimensional analysis of ozone and PM2.5 distributions obtained by observations of tethered balloon and unmanned aerial vehicle in Shanghai, China - Xiao-Bing Li; Dongfang Wang; Qing-Chang Lu; Zhong-Ren Peng; Qingyan Fu; Xiao-Ming Hu; Juntao Huo; Guangli Xiu; Bai Li; Chao Li; Dong-Sheng Wang; Hanyu Wang (Stochastic Environmental Research and Risk Assessment, 2018)

Failure mode and dynamic response of a double-sided slope with high water content of soil - Bing Yang; Fu-ping Gao; Dong-sheng Jeng (Journal of Mountain Science, 2018)

Gcn5‐dependent histone H3 acetylation and gene activity is required for the asexual development and virulence of Beauveria bassiana - Qing Cai; Juan‐Juan Wang; Bo Fu; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2018)
Summary Gcn5 is a core histone acetyltransferase that catalyzes histone H3 acetylation on N‐terminal lysine residues in yeasts and was reported to catalyze H3K9/K14 acetylation required for activating asexual development in Aspergillus . Here, we report a localization of Gcn5 ortholog in the nucleus and cytoplasm of Beauveria bassiana , a fungal insect pathogen. Deletion of gcn5 led to hypoacetylated H3 at K9/14/18/27 and 97% reduction in conidiation capacity as well as severe defects in colony growth and conidial thermotolerance. Two master conidiation genes, namely brlA and abaA , were transcriptionally repressed to undetectable level in Δ gcn5 , but sharply upregulated in wild‐type, at the beginning time of conidiation. Based on chromatin immunoprecipitation, both DNA and acetylation levels of the distal and proximal fragments of the brlA promoter bound by acetylated H3K14 alone were upregulated in wild‐type, but not in Δ gcn5 , at the mentioned time. In Δ gcn5 , normal cuticle infection was abolished while virulence through cuticle‐bypassing infection was greatly attenuated, accompanied by drastically reduced activities of putative cuticle‐degrading enzymes, retarded dimorphic transition and transcriptional repression of associated genes. These findings unveil a novel mechanism by which Gcn5 activates asexual development pathway by acetylating H3K14 and regulates the virulence‐related cellular events in B. bassiana .

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Transferability of Conceptual Hydrological Models Across Temporal Resolutions: Approach and Application - Meng-Xuan Jie; Hua Chen; Chong-Yu Xu; Qiang Zeng; Jie Chen; Jong-Suk Kim; Sheng-lian Guo; Fu-Qiang Guo (Water Resources Management, 2018)

Spike densities of the amygdala and neocortex reflect progression of kindled motor seizures - Yu-Lin Wang; Sheng-Fu Liang; Alvin W. Y. Su; Fu-Zen Shaw (Medical & Biological Engineering & Computing, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Drought Alleviated the Negative Effects of Elevated O3 on Lonicera maackii in Urban Area - Sheng Xu; Wei Fu; Xingyuan He; Wei Chen; Weiwei Zhang; Bo Li; Yanqing Huang (Bulletin of Environmental Contamination and Toxicology, 2017)

Leaf litter decomposition dynamics in unmanaged Phyllostachys pubescens stands at high elevations in the Daiyun Mountain National Nature Reserve - Dao-wei Xu; Jin-fu Liu; Peter Marshall; Zhong-sheng He; Shi-qun Zheng (Journal of Mountain Science, 2017)

Influence of Thread Design on Dental Implant Osseointegration Assayed Using the Lan-Yu Mini-Pig Model - Shih-Kang Chien; Shui-Sang Hsue; Chih-Shing Lin; Tzong-Fu Kuo; Duen-Jeng Wang; Jen-Chang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Increasing acidity of rain in subtropical tea plantation alters aluminum and nutrient distributions at the root-soil interface and in plant tissues - Xiao-Fei Hu; Fu-Sheng Chen; Michael L. Wine; Xiang-Min Fang (Plant and Soil, 2017)

Long-Term Generation Scheduling of Hydropower System Using Multi-Core Parallelization of Particle Swarm Optimization - Sheng-li Liao; Ben-xi Liu; Chun-tian Cheng; Zhi-fu Li; Xin-yu Wu (Water Resources Management, 2017)

Evaluation of Osseointegration in Titanium and Zirconia-Based Dental Implants with Surface Modification in a Miniature Pig Model - Tzong-Fu Kuo; Hung-Chieh Lu; Chien-Fang Tseng; Jen-Chang Yang; Sea-Fue Wang; Thomas Chung-Kuang Yang; Sheng-Yang Lee (Journal of Medical and Biological Engineering, 2017)

Serum Protein-Based Profiles as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease - Shu Yu; Yue-Ping Liu; Hai-Liang Liu; Jie Li; Yang Xiang; Yu-Hui Liu; Shu-Sheng Jiao; Lu Liu; Yajiang Wang; Weiling Fu (Molecular Neurobiology, 2017)

Hydrogen enhances adaptation of rice seedlings to cold stress via the reestablishment of redox homeostasis mediated by miRNA expression - Sheng Xu; Yilong Jiang; Weiti Cui; Qijiang Jin; Yihua Zhang; Duo Bu; Jiangyan Fu; Ren Wang; Feng Zhou; Wenbiao Shen (Plant and Soil, 2017)

Upper Cretaceous alluvial fan deposits in the Jianglangshan Geopark of Southeast China: implications for bedrock control on Danxia landform evolution - Liu-qin Chen; Fu-sheng Guo (Journal of Mountain Science, 2017)

Two new ent -atisane diterpenoids from the whole plants of Euphorbia wallichii - Yi Kuang; Shen-Yuan Fu; Fei Wang; Fu-Cai Ren; Dong-Feng Yang; Sheng-Xiang Yang; Yuan Gao (Natural Product Research, 2017)

Cone-shaped source characteristics and inductance effect of transient electromagnetic method - Hai-Yan Yang; Feng-Ping Li; Jian-Hua Yue; Fu-Sheng Guo; Xu-Hua Liu; Hua Zhang (Applied Geophysics, 2017)

Mycorrhizal colonization status of lowland rice (Oryza sativa L.) in the southeastern region of China - Xun-Wen Chen; Fu-Yong Wu; Hui Li; Wai-Fung Chan; Sheng-Chun Wu; Ming-Hung Wong (Environmental Science and Pollution Research, 2017)

Reducing N losses through surface runoff from rice-wheat rotation by improving fertilizer management - Yansheng Cao; Huifeng Sun; Yaqin Liu; Zishi Fu; Guifa Chen; Guoyan Zou; Sheng Zhou (Environmental Science and Pollution Research, 2017)

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.

Seroprevalence and risk factors of bovine viral diarrhoea virus (BVDV) infection in yaks (Bos grunniens) in northwest China - Jian-Gang Ma; Wei Cong; Fu-Heng Zhang; Sheng-Yong Feng; Dong-Hui Zhou; Yi-Ming Wang; Xing-Quan Zhu; Hong Yin; Gui-Xue Hu (Tropical Animal Health and Production, 2016)

Temporal stability analysis of surface soil water content on two karst hillslopes in southwest China - Sheng Wang; Hong Song Chen; Zhiyong Fu; Kelin Wang (Environmental Science and Pollution Research, 2016)

Modeling daily reference ET in the karst area of northwest Guangxi (China) using gene expression programming (GEP) and artificial neural network (ANN) - Sheng Wang; Zhi-yong Fu; Hong-song Chen; Yun-peng Nie; Ke-lin Wang (Theoretical and Applied Climatology, 2016)

Variables Affecting Fusion Rates in the Rat Posterolateral Spinal Fusion Model with Autogenic/Allogenic Bone Grafts: A Meta-analysis - Wataru Ishida; Benjamin D. Elder; Christina Holmes; Sheng-Fu L. Lo; Timothy F. Witham (Annals of Biomedical Engineering, 2016)

A sensitive immunochromatographic assay using colloidal gold–antibody probe for rapid detection of fumonisin B 1 in corn - Xi-Chun Wang; Hai-Xin Fan; Meng-Xue Fan; Fu-Hui Li; Shi-Bin Feng; Jin-Chun Li; Jin-Jie Wu; Yu Li; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2016)

Late Quaternary glacial advances in the eastern Qilianshan, north‐eastern Tibet, as inferred from luminescence dating of fluvioglacial sediments - Gang Hu; Chao‐Lu Yi; Jia‐Fu Zhang; Jin‐Hua Liu; Tao Jiang; Sheng‐Hua Li (Journal of Quaternary Science, 2016)
The Qilianshan [ shan means ‘mountain(s)’ in Chinese] are important for understanding the Quaternary glaciations which occurred along the north‐eastern margins of the Tibetan Plateau (TP). Two sets of moraines identified in the Gangshika Valley on the southern slopes of the Qilianshan, and in the Jindonggou Valley on the northern slopes of the Lenglongling Ridge in the eastern Qilianshan, were dated using optically stimulated luminescence (OSL) dating. The D e values of the sediments were determined using single aliquot regeneration (SAR) and ‘global standardized growth curve’ (gSGC) procedures. The gSGC method was first applied to glacial sediment and proved to be adaptable. Based on D e distribution analysis, and a comparison between the ages of coarse‐grained (90–125 μm) quartz, we concluded that the minimum age model (MAM) OSL age obtained may be closer to the burial age of the sediments. The first set of moraines in the Gangshika Valley was formed at 18.1 ± 1.8 ka. The second set of moraines in both the Gangshika and the Jindonggou valleys was mainly formed at ∼12.5–10.7 ka, consistent with the Younger Drays chronozone, most probably covering the moraines produced at 14.3 ± 1.4 ka. These results indicate that the glaciers along the Lenglongling Ridge were sensitive to abrupt decreases in temperature.

Degradation of litter quality and decline of soil nitrogen mineralization after moso bamboo (Phyllostachys pubscens) expansion to neighboring broadleaved forest in subtropical China - Qing-ni Song; Ming Ouyang; Qing-pei Yang; Hui Lu; Guang-yao Yang; Fu-sheng Chen; Jian-Min Shi (Plant and Soil, 2016)

Molecular characterization of two divergent variants of sugarcane bacilliform viruses infecting sugarcane in China - Sheng-Ren Sun; Mona B. Damaj; Olufemi J. Alabi; Xiao-Bin Wu; T. Erik Mirkov; Hua-Ying Fu; Ru-Kai Chen; San-Ji Gao (European Journal of Plant Pathology, 2016)

Airborne polybrominated diphenyl ethers (PBDEs), polybrominated dibenzo-p-dioxins/furans (PBDD/Fs), and dechlorane plus (DP) in concentrated vehicle parking areas - Huiru Li; Hehuan Liu; Ligui Mo; Guoying Sheng; Jiamo Fu; Ping’an Peng (Environmental Science and Pollution Research, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

CH4 Emission in Response to Water-Saving and Drought-Resistance Rice (WDR) and Common Rice Varieties under Different Irrigation Managements - Huifeng Sun; Sheng Zhou; Xiangfu Song; Zishi Fu; Guifa Chen; Jining Zhang (Water, Air, & Soil Pollution, 2016)

Measurement of aerosol effective density by single particle mass spectrometry - GuoHua Zhang; XinHui Bi; BingXue Han; Ning Qiu; ShouHui Dai; XinMing Wang; GuoYing Sheng; JiaMo Fu (Science China Earth Sciences, 2016)

The association between diurnal temperature range and childhood bacillary dysentery - Li-ying Wen; Ke-fu Zhao; Jian Cheng; Xu Wang; Hui-hui Yang; Ke-sheng Li; Zhi-wei Xu; Hong Su (International Journal of Biometeorology, 2016)

Evolution of the Late Cretaceous Yongfeng-Chongren Basin in Jiangxi Province, southeast China: insights from sedimentary facies analysis and pebble counting - Liu-qin Chen; Fu-sheng Guo; Chao Tang (Journal of Mountain Science, 2016)

Enhancement of naphthalene tolerance in transgenic Arabidopsis plants overexpressing the ferredoxin-like protein (ADI1) from rice - Xiao-Yan Fu; Bo Zhu; Hong-Juan Han; Wei Zhao; Yong-Sheng Tian; Ri-He Peng; Quan-Hong Yao (Plant Cell Reports, 2016)

Distribution of polybrominated diphenyl ethers and HBCD in sediments of the Hunhe River in Northeast China - Jiao Su; Yingzhuan Lu; Zhiyang Liu; Shutao Gao; Xiangying Zeng; Zhiqiang Yu; Guoying Sheng; Jia-mo Fu (Environmental Science and Pollution Research, 2015)

Characterization and expression analysis of Calmodulin (CaM) in orange-spotted grouper (Epinephelus coioides) in response to Vibrio alginolyticus challenge - Sheng-Wei Luo; Fu-Xing Xie; Yuan Liu; Wei-Na Wang (Ecotoxicology, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Improving Rice Ability to Degrade Different Polycyclic Aromatic Hydrocarbons Through Multigene Transformation of a Hybrid Dioxygenase System - Ri-He Peng; Biao Shi; Xiao-Yan Fu; Yong-Sheng Tian; Wei Zhao; Bo Zhu; Jing Xu; Hong-Juan Han; Zhong-Yi Yuan; Kai-Hong Liu; Quan-Hong Yao (Plant Molecular Biology Reporter, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Hydrogeochemical and isotopic characteristics of groundwater in the salt chemical industrial base of Guyuan City, northwestern China - Ying Li; Fu Sheng Hu; Zhong Qi Xue; Yan Qing Yu; Ping Wu (Arabian Journal of Geosciences, 2015)

Ecological species groups and interspecific association of dominant tree species in Daiyun Mountain National Nature Reserve - Song-jin Su; Jin-fu Liu; Zhong-sheng He; Shi-qun Zheng; Wei Hong; Dao-wei Xu (Journal of Mountain Science, 2015)

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

Challenges and adaptations of farming to climate change in the North China Plain - Hai-Lin Zhang; Xin Zhao; Xiao-Gang Yin; Sheng-Li Liu; Jian-Fu Xue; Meng Wang; Chao Pu; Rattan Lal; Fu Chen (Climatic Change, 2015)

Auto-pick first breaks with complex raypaths for undulate surface conditions - Sheng-Pei An; Tian-Yue Hu; Yong-Fu Cui; Wen-Sheng Duan; Geng-Xin Peng (Applied Geophysics, 2015)

Mapping of quantitative trait loci for cold tolerance at the early seedling stage in landrace rice Xiang 743 - Wenqiang Liu; Tingting Lu; Yongchao Li; Xiaowu Pan; Yonghong Duan; Jun Min; Xiqin Fu; Xinnian Sheng; Junzhi Xiao; Sanxiong Liu; Jiang Tan; Yi Yao; et al. (Euphytica, 2015)

Enantiomeric composition of polycyclic musks in sediments from the Pearl River and Suzhou Creek - Han Song; Xiangying Zeng; Zhiqiang Yu; Delin Zhang; Shuxia Cao; Wenlan Shao; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2015)

Characteristics of Dew Formation and Distribution, and Its Contribution to the Surface Water Budget in a Semi-arid Region in China - Qiang Zhang; Sheng Wang; Fu-Lin Yang; Ping Yue; Tong Yao; Wen-Yu Wang (Boundary-Layer Meteorology, 2015)

Spatial distribution of heavy metal contamination in soils near a primitive e-waste recycling site - Sheng-Xiang Quan; Bo Yan; Fan Yang; Ning Li; Xian-Ming Xiao; Jia-Mo Fu (Environmental Science and Pollution Research, 2015)

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Comparison of elemental and black carbon measurements during normal and heavy haze periods: implications for research - Guorui Zhi; Yingjun Chen; Zhigang Xue; Fan Meng; Jing Cai; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Assessment of carbon sustainability under different tillage systems in a double rice cropping system in Southern China - Jian-Fu Xue; Sheng-Li Liu; Zhong-Du Chen; Fu Chen; Rattan Lal; Hai-Ming Tang; Hai-Lin Zhang (The International Journal of Life Cycle Assessment, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

Biological monitoring of environmental exposure to polycyclic aromatic hydrocarbons in subjects living in the area of recycling electronic garbage, in Southern China - Yu Wang; Wenbing Zhang; Ruifang Fan; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2014)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Effect of bone marrow-derived CD11b+F4/80+ immature dendritic cells on the balance between pro-inflammatory and anti-inflammatory cytokines in DBA/1 mice with collagen-induced arthritis - Jingjing Fu; Lingling Zhang; Shanshan Song; Kangliang Sheng; Ying Li; Peipei Li; Shasha Song; Qingtong Wang; Jianhong Chu; Wei Wei (Inflammation Research, 2014)

Re–Os isotope and platinum-group element geochemistry of the Pobei Ni–Cu sulfide-bearing mafic–ultramafic complex in the northeastern part of the Tarim Craton - Sheng-Hong Yang; Mei-Fu Zhou; Peter C. Lightfoot; Ji-Feng Xu; Christina Yan Wang; Chang-Yi Jiang; Wen-Jun Qu (Mineralium Deposita, 2014)

Inhibition of human glioma U251 cells growth in vitro and in vivo by hydroxyapatite nanoparticle-assisted delivery of short hairpin RNAs against SATB1 - Sheng-Hua Chu; Zhang-Ming Zhou; Dong-Fu Feng; Yan-Bin Ma (Molecular Biology Reports, 2014)

Diagnosis of the secondary circulation of tropical storm Bilis (2006) and the effects of convective systems on its track - Jinhua Yu; Hao Fu; Sheng Tang; Siwei Sheng (Journal of Meteorological Research, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

Study on elastic P-wave propagation law in unfavorable geologic structures with discontinuous deformation analysis method - Y. H. Zhang; X. D. Fu; Q. Sheng; X. L. Leng (Arabian Journal of Geosciences, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Promoting role of an endophyte on the growth and contents of kinsenosides and flavonoids of Anoectochilus formosanus Hayata, a rare and threatened medicinal Orchidaceae plant - Fu-sheng Zhang; Ya-li Lv; Yue Zhao; Shun-xing Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Developmental expression and possible functional roles of mouse Nlrp4e in preimplantation embryos - Bo-hao Chang; Xu Liu; Jun Liu; Fu-sheng Quan; Ze-kun Guo; Yong Zhang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

A Novel Endogenous Induction of ColE7 Expression in a csrA Mutant of Escherichia coli - Hao-Wei Chang; Tsung-Yeh Yang; Guang-Sheng Lei; Kin-Fu Chak (Current Microbiology, 2013)

Ribonuclease 4 protects neuron degeneration by promoting angiogenesis, neurogenesis, and neuronal survival under stress - Shuping Li; Jinghao Sheng; Jamie K. Hu; Wenhao Yu; Hiroko Kishikawa; Miaofen G. Hu; Kaori Shima; David Wu; Zhengping Xu; Winnie Xin; Katherine B. Sims; John E. Landers; et al. (Angiogenesis, 2013)

Complementary screening, identification and application of a novel class II 5-enopyruvylshikimate-3-phosphate synthase from Bacillus cereus - Yong-Sheng Tian; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Quan-Hong Yao (World Journal of Microbiology and Biotechnology, 2013)

Characteristics, loss and gain of atmospheric carbonyl compounds in winters of 2008–2010 in Pearl River Delta region, China - Yonglin Liu; Xinhui Bi; L. Y. Chan; Sheng Wen; Xinming Wang; Guoying Sheng; Jiamo Fu (Journal of Atmospheric Chemistry, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Tissue concentrations, bioaccumulation, and biomagnification of synthetic musks in freshwater fish from Taihu Lake, China - Xiaolan Zhang; Qing Xu; Shoukuan Man; Xiangying Zeng; Yingxin Yu; Yuping Pang; Guoying Sheng; Jiamo Fu (Environmental Science and Pollution Research, 2013)

Measuring δ 13 C values of atmospheric acetaldehyde via sodium bisulfite adsorption and cysteamine derivatisation - Songjun Guo; Mei Chen; Sheng Wen; Guoying Sheng; Jiamo Fu (Isotopes in Environmental and Health Studies, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Protective effect of low-molecular-weight heparin on pancreatic encephalopathy in severe acute pancreatic rats - Fu Qiu; Xin-sheng Lu; Yu-kun Huang (Inflammation Research, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Leaf traits and relationships differ with season as well as among species groupings in a managed Southeastern China forest landscape - Fu-Sheng Chen; Karl J. Niklas; Guang-Sheng Chen; Dali Guo (Plant Ecology, 2012)

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Water quality criteria for 4-nonylphenol in protection of aquatic life - BingLi Lei; Qian Liu; YanFeng Sun; YiPei Wang; ZhiQiang Yu; XiangYing Zeng; JiaMo Fu; GuoYing Sheng (Science China Earth Sciences, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Basin-scale groundwater response to precipitation variation and anthropogenic pumping in Chih-Ben watershed, Taiwan - Kuo-Chin Hsu; Hsin-Fu Yeh; You-Cheng Chen; Cheng-Haw Lee; Chung-Ho Wang; Feng-Sheng Chiu (Hydrogeology Journal, 2012)

Analysis of gene expression profile of Arabidopsis genes under trichloroethylene stresses with the use of a full-length cDNA microarray - Bo Zhu; Ri-He Peng; Ai-Sheng Xiong; Xiao-Yan Fu; Wei Zhao; Yong-Sheng Tian; Xiao-Fen Jin; Yong Xue; Jing Xu; Hong-Juan Han; Chen Chen; Jian-Jie Gao; et al. (Molecular Biology Reports, 2012)

Cloning and characterization of a maize bZIP transcription factor, ZmbZIP72, confers drought and salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Jing Fu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Planta, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Effects of different elicitors on yield of tropane alkaloids in hairy roots of Anisodus acutangulus - Guoyin Kai; Sheng Yang; Yan Zhang; Xiuqin Luo; Xueqing Fu; Ang Zhang; Jianbo Xiao (Molecular Biology Reports, 2012)

Bp5250 inhibits vascular endothelial growth factor-induced angiogenesis and HIF-1α expression on endothelial cells - Kuan-Ting Lin; Jin-Cherng Lien; Ching-Hu Chung; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Analysis of the expression of BohLOL1, which encodes an LSD1-like zinc finger protein in Bambusa oldhamii - Sheng-Hsiung Yeh; Choun-Sea Lin; Fu-Hui Wu; Ai-Yu Wang (Planta, 2011)

Contamination, source identification, and risk assessment of polycyclic aromatic hydrocarbons in agricultural soil of Shanghai, China - YuFeng Jiang; XueTong Wang; MingHong Wu; GuoYing Sheng; JiaMo Fu (Environmental Monitoring and Assessment, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

High expression of recombinant Streptomyces sp. S38 xylanase in Pichia pastoris by codon optimization and analysis of its biochemical properties - Xiao-Yan Fu; Wei Zhao; Ai-Sheng Xiong; Yong-Sheng Tian; Ri-He Peng (Molecular Biology Reports, 2011)

Soil phosphorus fractions and tree phosphorus resorption in pine forests along an urban-to-rural gradient in Nanchang, China - Xiao-Fei Hu; Fu-Sheng Chen; Gregory Nagle; Yun-Ting Fang; Ming-Quan Yu (Plant and Soil, 2011)

Resveratrol attenuates apoptosis of pulmonary microvascular endothelial cells induced by high shear stress and proinflammatory factors - Liang Xia; Fang Ding; Jun-Hui Zhu; Guo-Sheng Fu (Human Cell, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

Functional identification of hyoscyamine 6β-hydroxylase from Anisodus acutangulus and overproduction of scopolamine in genetically-engineered Escherichia coli - Guoyin Kai; Yuanyuan Liu; Xiaoyun Wang; Sheng Yang; Xueqing Fu; Xiuqin Luo; Pan Liao (Biotechnology Letters, 2011)

Delineation of the translocation of colicin E7 across the inner membrane of Escherichia coli - Yuh-Ren Chen; Tsung-Yeh Yang; Guang-Sheng Lei; Lung-JR Lin; Kin-Fu Chak (Archives of Microbiology, 2011)

Isolation and characterization of polymorphic microsatellite markers for the ariake icefish (Salanx ariakensis kishinouye) - Juan Hu; Sheng-Jie Ren; Cui-Zhang Fu; Xiao-Ling Gong (Conservation Genetics Resources, 2011)

Important foliar traits depend on species-grouping: analysis of a remnant temperate forest at the Keerqin Sandy Lands, China - Fu-Sheng Chen; Karl J. Niklas; De-Hui Zeng (Plant and Soil, 2011)

Differential expression of expressed sequence tags in alfalfa roots under aluminum stress - Fu Fan; Xin-Wei Li; Yue-Ming Wu; Zhuo-Sheng Xia; Jin-Jun Li; Wen Zhu; Jin-Xin Liu (Acta Physiologiae Plantarum, 2011)

Semi-rational site-directed mutagenesis of phyI1s from Aspergillus niger 113 at two residue to improve its phytase activity - Yong-Sheng Tian; Ri-He Peng; Jing Xu; Wei Zhao; Feng Gao; Xiao-Yan Fu; Ai-Sheng Xiong; Quan-Hong Yao (Molecular Biology Reports, 2011)

RNA interference targeting CITRON can significantly inhibit the proliferation of hepatocellular carcinoma cells - Yinghui Fu; Jian Huang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular Biology Reports, 2011)

Polycyclic aromatic hydrocarbons in the atmosphere of Shanghai, China - Yingjun Chen; Yanli Feng; Shengchun Xiong; Dongyan Liu; Gang Wang; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Quantitative trait loci analysis for rice seed vigor during the germination stage - Zhou-fei Wang; Jian-fei Wang; Yong-mei Bao; Fu-hua Wang; Hong-sheng Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Influences of host species on transpiration, photosynthesis, chlorophyll and mineral contents of medicinal hemiparasite Thesium chinense Turcz - Fu Lai Luo; Qiao Sheng Guo (Acta Physiologiae Plantarum, 2010)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

Occurrence and distribution of polycyclic aromatic carbons in sludges from wastewater treatment plants in Guangdong, China - Xiangying Zeng; Zheng Lin; Hongyan Gui; Wenlan Shao; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Environmental Monitoring and Assessment, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Fabrication of Balloon-Expandable Self-Lock Drug-Eluting Polycaprolactone Stents Using Micro-Injection Molding and Spray Coating Techniques - Shih-Jung Liu; Fu-Jun Chiang; Chao-Ying Hsiao; Yi-Chuan Kau; Kuo-Sheng Liu (Annals of Biomedical Engineering, 2010)

Cavitation Phenomena in Mechanical Heart Valves: Studied by Using a Physical Impinging Rod System - Chi-Wen Lo; Sheng-Fu Chen; Chi-Pei Li; Po-Chien Lu (Annals of Biomedical Engineering, 2010)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Research on flux of dry atmospheric falling dust and its characterization in a subtropical city, Guangzhou, South China - Jinping Zhao; Ping’an Peng; Jianzhong Song; Shexia Ma; Guoying Sheng; Jiamo Fu (Air Quality, Atmosphere & Health, 2010)

Response of leaf anatomy of Chenopodium acuminatum to soil resource availability in a semi-arid grassland - Fu-Sheng Chen; De-Hui Zeng; Timothy J. Fahey; Cheng-Yi Yao; Zhan-Yuan Yu (Plant Ecology, 2010)

Seasonal variation, source, and regional representativeness of the background aerosol from two remote sites in western China - Wenjun Qu; Dan Wang; Yaqiang Wang; Lifang Sheng; Gang Fu (Environmental Monitoring and Assessment, 2010)

NP-184[2-(5-methyl-2-furyl) benzimidazole], a novel orally active antithrombotic agent with dual antiplatelet and anticoagulant activities - Heng-Lan Kuo; Jin-Cherng Lien; Ching-Hu Chung; Chien-Hsin Chang; Shyh-Chyi Lo; I-Chun Tsai; Hui-Chin Peng; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Analysis of Brassica rapa ESTs: gene discovery and expression patterns of AP2/ERF family genes - Jing Zhuang; Ai-Sheng Xiong; Ri-He Peng; Feng Gao; Bo Zhu; Jian Zhang; Xiao-Yan Fu; Xiao-Feng Jin; Jian-Min Chen; Zhen Zhang; Yu-Shan Qiao; Quan-Hong Yao (Molecular Biology Reports, 2010)

The reversed terminator of octopine synthase gene on the Agrobacterium Ti plasmid has a weak promoter activity in prokaryotes - Jun-Li Shao; Yue-Sheng Long; Gu Chen; Jun Xie; Zeng-Fu Xu (Molecular Biology Reports, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

A method of detecting carbonyl compounds in tree leaves in China - Juan Huang; Yanli Feng; Jiamo Fu; Guoying Sheng (Environmental Science and Pollution Research, 2010)

Mutations in two amino acids in phyI1s from Aspergillus niger 113 improve its phytase activity - Yong-Sheng Tian; Ri-He Peng; Jing Xu; Wei Zhao; Feng Gao; Xiao-Yan Fu; Ai-Sheng Xiong; Quan-Hong Yao (World Journal of Microbiology and Biotechnology, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Nucleotide diversity and molecular evolution of the PSY1 gene in Zea mays compared to some other grass species - Zhiyuan Fu; Jianbing Yan; Yanping Zheng; Marilyn L. Warburton; Jonathan H. Crouch; Jian-Sheng Li (Theoretical and Applied Genetics, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Digenean parasites of Chinese marine fishes: a list of species, hosts and geographical distribution - Sheng-fa Liu; Wen-feng Peng; Peng Gao; Ming-jun Fu; Han-zhou Wu; Ming-ke Lu; Ji-qing Gao; Jun Xiao (Systematic Parasitology, 2010)

Tetrahydroxy stilbene glucoside reduces the cognitive impairment and overexpression of amyloid precursor protein induced by aluminum exposure - Hong-Bo Luo; Jin-Sheng Yang; Xiang-Qun Shi; Xue-Feng Fu; Qi-Dong Yang (Neuroscience Bulletin, 2009)

Polychlorinated Biphenyls in the Atmosphere of an Urban City: Levels, Distribution, and Emissions - Laiguo Chen; Xiaochun Peng; Yumei Huang; Zhencheng Xu; Bixian Mai; Guoying Sheng; Jiamo Fu; Xinhua Wang (Archives of Environmental Contamination and Toxicology, 2009)

Stabilization of hepatocyte growth factor mRNA by hypoxia-inducible factor 1 - Sheng-Hua Chu; Dong-Fu Feng; Yan-Bin Ma; Zhi-An Zhu; Hong Zhang; Jian-Hua Qiu (Molecular Biology Reports, 2009)

Effects of temperature parameters on thermal-optical analysis of organic and elemental carbon in aerosol - Guorui Zhi; Yingjun Chen; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2009)

Molecular cloning and characterization of a novel transcript variant of Mtsarg1 gene - Li Li; Gang Liu; Jun-Jiang Fu; Lu-Yun Li; Xiao-Jun Tan; Sheng Yang; Guang-Xiu Lu (Molecular Biology Reports, 2009)

Extensive population expansion of Pedicularis longiflora (Orobanchaceae) on the Qinghai‐Tibetan Plateau and its correlation with the Quaternary climate change - FU‐SHENG YANG; YU‐FEI LI; XIN DING; XIAO‐QUAN WANG (Molecular Ecology, 2008)
The Qinghai‐Tibetan Plateau (QTP) is thought to be more strongly affected by the Quaternary glaciations than most other regions of the same latitude. It would be of great interest to investigate the population genetic structure of organisms distributed on the platform and its correlation with the Quaternary climatic oscillations. Here we used the chloroplast (cp)DNA trn T‐ trn F sequence to study genetic variation and phylogeography of Pedicularis longiflora , an alpine herb with extensive distribution on the QTP. Based on a range‐wide sampling comprising 41 populations and 910 individuals, we detected 30 cpDNA haplotypes that were divided into five clades by phylogenetic and network analyses and a strong phylogeographical structure. All haplotypes but one in the three basal clades occur exclusively in the southeast QTP, whereas haplotypes in the young clade V occupy almost the whole species range. In particular, the young haplotype H18 occurs in 420 individuals, even at a frequency of 100% in some QTP platform populations and the Altai population. The haplotype distribution pattern, together with molecular clock estimation and mismatch distribution analysis, suggests that the southeast QTP was either a refuge for P . longiflora during the Quaternary climatic change or is the place of origin of the species. The present wide distribution of the species on the QTP platform has resulted from recent population expansions which could be dated back to 120 000–17 000 years ago, a period mostly before the last glacial maximum. The possible relationships among geographic genetic structure, climatic change and species diversification in Pedicularis are also discussed.

Hepatic and extrahepatic expression of estrogen-responsive genes in male adult zebrafish (Danio rerio) as biomarkers of short-term exposure to 17β-estradiol - Yuanxiang Jin; Wanyuan Wang; G. Daniel Sheng; Weiping Liu; Zhengwei Fu (Environmental Monitoring and Assessment, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Establishment of a cDNA library from Bambusa edulis Murno in vitro-grown shoots - Nein-Tzu Liu; Fu-Hui Wu; Hsin-Sheng Tsay; Wei-Chin Chang; Choun-Sea Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Characteristics of carbonyl compounds in ambient air of Shanghai, China - Juan Huang; Yanli Feng; Jian Li; Bin Xiong; Jialiang Feng; Sheng Wen; Guoying Sheng; Jiamo Fu; Minghong Wu (Journal of Atmospheric Chemistry, 2008)

Differentiation of commercial strains of Agaricus species in China with inter-simple sequence repeat marker - Xue-Juan Guan; Lu Xu; Yan-Chun Shao; Zhuo-Ren Wang; Fu-Sheng Chen; Xin-Chang Luo (World Journal of Microbiology and Biotechnology, 2008)

Trade-offs between constitutive and induced resistance in wild crucifers shown by a natural, but not an artificial, elicitor - Peng-Jun Zhang; Jin-Ping Shu; Cheng-Xin Fu; Yun Zhou; Ying Hu; Myron P. Zalucki; Shu-Sheng Liu (Oecologia, 2008)

Emission of volatile organic sulfur compounds from a heavily polluted river in Guangzhou, South China - Yanqing Sheng; Fanzhong Chen; Ying Yu; Xinming Wang; Guoying Sheng; Jiamo Fu; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Distribution, Source Apportionment, and Transport of PAHs in Sediments from the Pearl River Delta and the Northern South China Sea - Xiao-Jun Luo; She-Jun Chen; Bi-Xian Mai; Guo-Ying Sheng; Jia-Mo Fu; Eddy Y. Zeng (Archives of Environmental Contamination and Toxicology, 2008)

Adrenal myelolipoma within myxoid cortical adenoma associated with Conn’s syndrome - Lu Hong-sheng; Gan Mei-fu; Chen Han-song; Huang Shan-qiang (Journal of Zhejiang University-SCIENCE B, 2008)

Gene transfer into primary cultures of fetal neural stem cells by a recombinant adenovirus carrying the gene for green fluorescent protein - Yong Fu; Shen-qing Wang; Ying-peng Liu; Guo-peng Wang; Jian-ting Wang; Shu-sheng Gong (Journal of Zhejiang University-SCIENCE B, 2008)

Use of geochemical modeling to evaluate the hydraulic connection of aquifers: a case study from Chianan Plain, Taiwan - Hsueh-Yu Lu; Tsung-Kwei Liu; Wen-Fu Chen; Tsung-Ren Peng; Chung-Ho Wang; Meng-Hsun Tsai; Tai-Sheng Liou (Hydrogeology Journal, 2008)

Characteristics of atmospheric carbonyls and VOCs in Forest Park in South China - Yingxin Yu; Sheng Wen; Huixiong Lü; Yanli Feng; Xinming Wang; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2008)

Evaluation of FORS-D Analysis: A Comparison with the Statistically Significant Stem-loop Potential - Chi-Yu Zhang; Ji-Fu Wei; Jian-Sheng Wu; Wen-Rong Xu; Xiao Sun; Shao-Heng He (Biochemical Genetics, 2008)

Identification of functional candidate genes for drought tolerance in rice - Bin-Ying Fu; Jian-Hua Xiong; Ling-Hua Zhu; Xiu-Qin Zhao; Hua-Xue Xu; Yong-Ming Gao; Yang-Sheng Li; Jian-Long Xu; Zhi-Kang Li (Molecular Genetics and Genomics, 2007)

Evaluation of dermal absorption and protective effectiveness of respirators for xylene in spray painters - Fu-Kuei Chang; Mei-Lien Chen; Shu-Fang Cheng; Tung-Sheng Shih; I-Fang Mao (International Archives of Occupational and Environmental Health, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Isolation and characterization of a novel cDNA encoding ERF/AP2-type transcription factor OsAP25 from Oryza Sativa L. - Xiao-Yan Fu; Zhen Zhang; Ri-He Peng; Ai-Sheng Xiong; Jin-Ge Liu; Li-Juan Wu; Feng Gao; Hong Zhu; Zhao-Kui Guo; Quan-Hong Yao (Biotechnology Letters, 2007)

Isolation and characterization of microsatellite loci in Cryptocarya chinensis in lower subtropical China - Zheng-Feng Wang; Gang Li; Sheng-Lei Fu; Hai Ren (Conservation Genetics, 2007)

Protein kinase C-ζ regulation of GLUT4 translocation through actin remodeling in CHO cells - Xiao-Jun Liu; Chang Yang; Nishith Gupta; Jin Zuo; Yong-Sheng Chang; Fu-De Fang (Journal of Molecular Medicine, 2007)

Analysis of Protein Expression Profiles of Halobacillus dabanensis D-8T Under Optimal and High Salinity Conditions - De Qin Feng; Li Fu Yang; Wei Dong Lu; Su Sheng Yang (Current Microbiology, 2007)

Use of Remote-Trip Cameras for Wildlife Surveys and Evaluating the Effectiveness of Conservation Activities at a Nature Reserve in Sichuan Province, China - Wang Dajun; Li Sheng; William J. McShea; Li Ming Fu (Environmental Management, 2006)

Prediction of heterosis using QTLs for yield traits in rapeseed (Brassica napus L.) - Jin-Xiong Shen; Ting-Dong Fu; Guang-Sheng Yang; Jin-Xing Tu; Chao-Zhi Ma (Euphytica, 2006)

Chemical Composition and Sources of PM10 and PM2.5 Aerosols in Guangzhou, China - Xinhua Wang; Xinhui Bi; Guoying Sheng; Jiamo Fu (Environmental Monitoring and Assessment, 2006)

Anther culture and haploid plant regeneration in purple coneflower (Echinacea purpurea L.) - Fu-Cheng Zhao; Dahanayake Nilanthi; Yue-Sheng Yang; Hong Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Effects of dietary supplementation with Clostridium butyricum on the growth performance and humoral immune response in Miichthys miiuy - Zeng-fu Song; Tian-xing Wu; Li-sheng Cai; Li-jing Zhang; Xiao-dong Zheng (Journal of Zhejiang University-SCIENCE B, 2006)

Molecular validation of multiple allele inheritance for dominant genic male sterility gene in Brassica napus L - Lai-Qiang Song; Ting-Dong Fu; Jin-Xing Tu; Cao-Zhi Ma; Guang-Sheng Yang (Theoretical and Applied Genetics, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

The seasonal variabilities in the concentration of atmospheric aerosols over Qingdao, China - Lifang Sheng; Ying Fu; Mingyan Qiu; Huiwang Gao (Journal of Ocean University of China, 2005)

Detecting Epstein-Barr virus DNA from peripheral blood mononuclear cells in adult patients with systemic lupus erythematosus in Taiwan - Shan-Fu Yu; Huei-Chuin Wu; Wen-Chan Tsai; Jeng-Hsien Yen; Wen Chiang; Chung-Yee Yuo; Sheng-Nan Lu; Lien-Chai Chiang; Chung-Jen Chen (Medical Microbiology and Immunology, 2005)

Microbial Metabolism of Quinoline by Comamonas sp. - Mingchao Cui; Fanzhong Chen; Jiamo Fu; Guoying Sheng; Guoping Sun (World Journal of Microbiology and Biotechnology, 2004)

Relationship between resort life cycle and residents’ perception and attitude - Xiao-zhong Yang; Lin Lu; Guang-sheng Zhang; Song Lu; Guo-fu Xuan (Chinese Geographical Science, 2004)

Unexpected high divergence in nrDNA ITS and extensive parallelism in floral morphology of Pedicularis (Orobanchaceae) - Fu-Sheng Yang; Xiao-Quan Wang; De-Yuan Hong (Plant Systematics and Evolution, 2003)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

Biodegradability of Di(2-Ethylhexyl) Phthalate by Pseudomonas Fluorescens FS1 - Zeng Feng; Cui Kunyan; Fu Jiamo; Sheng Guoying; Yang Huifang (Water, Air, & Soil Pollution, 2002)

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Distribution of Polycyclic Aromatic Hydrocarbons in Aerosols and Dustfall in Macao - Qi Shihua; Yan Jun; Zhang Gan; Fu Jiamo; Sheng Guoying; Wang Zhishi; S. M. Tong; U. W. Tang; Min Yunshun (Environmental Monitoring and Assessment, 2001)

Responses of soil nutrient to driving mechanism in Taihu Lake basin in last 20 years - Chen Fu; Peng Bu-zhuo; Bao Hao-sheng (Journal of Geographical Sciences, 2001)

Characterizing the cytoplasmic diversity and phyletic relationship of Chinese landraces of soybean, Glycine max, based on RFLPs of chloroplast and mitochondrial DNA - Yoshiya Shimamoto; Jun Abe; Zhong Gao; Junyi Gai; Fu-Sheng Thseng (Genetic Resources and Crop Evolution, 2000)

Seasonal variations of riverine organic carbon contents in Makou and Hekou gauge stations of the Zhujiang River, China - Quan-zhou Gao; Cheng-de Shen; Yan-min Sun; Wei-xi Yi; Jia-mo Fu; Guo-ying Sheng (Chinese Geographical Science, 2000)

A renewable energy source — hydrocarbon gases resulting from pyrolysis of the marine nanoplanktonic alga Emiliania huxleyi - Qingyu Wu; Junbiao Dai; Yoshihiro Shiraiwa; Guoying Sheng; Jiamo Fu (Journal of Applied Phycology, 1999)

Molecular indicators of microbial contributions to recent and Tertiary hypersaline lacustrine sediments in China - Ruiliang Wang; Simon C. Brassell; Jiamo Fu; Guoying Sheng (Hydrobiologia, 1998)

Background exposure of urban populations to lead and cadmium: comparison between China and Japan - Y.-Q. Wu; Zuo-Wen Zhang; Chan-Seok Moon; Shinichro Shimbo; Takao Watanabe; Feng-Sheng He; Shun-Fu Zhou; Jiang-Bin Qu; M. Ikeda; De-Ming Su (International Archives of Occupational and Environmental Health, 1997)

Organochlorinated Compounds in Waters of the Pearl River Delta Region - Yang Yanhong; Sheng Guoying; Fu Jimo; Min Yushun (Environmental Monitoring and Assessment, 1997)

Determination of Trace Organochlorinated Pesticides and Polychlorinated Biphenyls in Water - Zou Shichun; Zhang Zhanxia; Sheng Guoying; Min Yushun; Fu Jiamo (Environmental Monitoring and Assessment, 1997)